Organic EL display device
By using a multi-layer structure of a negative and positive photosensitive composition in the pixel segmentation layer, the problem that high light emitting reliability is difficult to achieve in the prior art is solved, especially in the case of an opening with a narrow opening width, a combination of high light shading and high light emitting reliability is achieved.
Patent Information
- Application Number
- CN202280067491.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-10-18
- Filing Date
- 2022-09-01
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-09-01
AI Technical Summary
In the prior art, it is difficult to achieve high light emission reliability using a pixel segmentation layer formed using a negative photosensitive composition, especially in the case of an opening with a narrow opening width.
A pixel segmentation layer of a multi-layer structure consisting of a negative photosensitive composition (a) and a positive photosensitive composition (b) is used, wherein the layer (A) contains a cured product of the negative photosensitive composition and covers the layer (B) on its surface.
It is achieved that high light luminous reliability is maintained while having high light shading, especially in the case of an opening portion with a narrow opening width.
Smart Images

Figure CN118077312B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an organic EL display device. Background Art
[0002] Many products equipped with organic electroluminescent (EL) display devices such as smart phones, televisions, and car monitors have been developed. In recent years, for the purpose of improving the visual recognition and contrast of organic EL display devices, in order to suppress the color mixing caused by light leakage into adjacent luminescent pixels, the reflection of external light such as sunlight, etc., the technology of blackening the pixel segmentation layer to give light shielding properties has attracted attention. In addition, it is further required to achieve high precision of the display unit by reducing the size of the luminescent pixels. Each luminescent pixel of red / green / blue is formed in the opening of the patterned pixel segmentation layer having the function of an insulating layer. Therefore, in order to configure a large number of small luminescent pixels in the surface of the display unit, it is necessary to form a pattern of a pixel segmentation layer with a large number of openings with narrow opening widths. The pixel segmentation layer is usually formed by a photolithography method using a photosensitive composition. As a photosensitive composition for forming a black pixel segmentation layer, for example, Patent Document 1 discloses a negative photosensitive composition containing an organic black pigment, and discloses an organic EL display device having a pixel segmentation layer formed using it.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: International Publication No. 2021 / 111860 Summary of the invention
[0006] Problems to be solved by the invention
[0007] However, there is a problem that when a pixel dividing layer having an opening with a narrow opening width is formed using the negative photosensitive composition disclosed in Patent Document 1, high light emission reliability cannot be obtained.
[0008] For the above reasons, there is an urgent need for an organic EL display device having a high light shielding property and high light emission reliability despite having a pixel segmentation layer having an opening portion with a narrow opening width.
[0009] Means for solving problems
[0010] The present invention is as follows.
[0011] (1) An organic EL display device comprising, in order, a substrate, a planarization layer, a first electrode, a pixel division layer, a light-emitting pixel, and a second electrode, wherein the pixel division layer comprises a layer (A) and a layer (B);
[0012] The layer (A) is a layer arranged on the surface of the first electrode so that the surface of the first electrode is partially exposed, and the layer (B) is a layer arranged on at least a part of the surface of the layer (A).
[0013] The layer (A) contains a cured product of a negative photosensitive composition (a), wherein the negative photosensitive composition (a) contains: a pigment and / or a dye; a compound having two or more ethylenically unsaturated double bond groups in the molecule; and a photopolymerization initiator, and the layer (B) contains a cured product of a positive photosensitive composition (b), wherein the positive photosensitive composition (b) contains a resin and a photoacid generator.
[0014] (2) The organic EL display device according to (1), wherein the display portion has a portion where the area ratio of the surface of the layer (A) covered by the layer (B) is 20 to 100% of the total surface area of the layer (A) (100%).
[0015] (3) The organic EL display device according to (1) or (2), further comprising a color filter on the light extraction side of the light-emitting pixel.
[0016] (4) The organic EL display device according to any one of (1) to (3), wherein the layer (A) has an opening area of 30.0 to 260.0 μm in which the light-emitting pixels are arranged in the display portion. 2 The opening of the
[0017] (5) The organic EL display device according to any one of (1) to (4), wherein the cured product of the positive photosensitive composition (b) contains a resin having an imide bond and / or a benzoxazole skeleton.
[0018] (6) The organic EL display device according to any one of (1) to (5), wherein the cured product of the negative photosensitive composition (a) contains the pigment, and the pigment contains a benzodifuranone-based black pigment represented by the formula (1) or (2) described below.
[0019] (7) An organic EL display device as described in any one of (1) to (6), wherein the cured product of the negative photosensitive composition (a) further contains at least one perylene-based organic pigment selected from the group consisting of CI Pigment Red 123, CI Pigment Red 149, CI Pigment Red 178, CI Pigment Red 179, CI Pigment Red 190, CI Pigment Violet 29 and 3,4,9,10-perylenetetracarboxylic acid bisbenzimidazole.
[0020] (8) The organic EL display device according to any one of (1) to (7), wherein the cured product of the negative photosensitive composition (a) further contains bisbenzimidazole-3,4,9,10-perylenetetracarboxylate.
[0021] (9) An organic EL display device as described in any one of (1) to (8), wherein, in a portion where the aforementioned layer (B) is arranged on the surface of the aforementioned layer (A), the maximum film thickness of the aforementioned layer (A) is 0.5 to 3.0 μm, and the maximum film thickness of the aforementioned layer (B) is 0.1 to 3.0 μm.
[0022] (10) The organic EL display device according to any one of (1) to (9), wherein the optical density per 1 μm of the film thickness of the layer (A) (OD / μm) is 0.5 to 1.5.
[0023] (11) An organic EL display device as described in any one of (1) to (10), wherein the cured product of the negative photosensitive composition (a) contains silica particles having a primary particle size of 5 to 30 nm and an aspect ratio (major axis / minor axis) of 1.0 to 1.5.
[0024] Effects of the Invention
[0025] According to the present invention, there is provided an organic EL display device having high light shielding properties and high light emission reliability despite having a pixel division layer having an opening portion with a narrow opening width. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] [ Figure 1 ] is a cross-sectional view of a TFT substrate in an organic EL display device listed as a specific example of an embodiment of the present invention.
[0027] [ Figure 2 ] is a cross-sectional view of a color filter substrate that can be included in an organic EL display device, which is listed as a specific example of an embodiment of the present invention.
[0028] [ Figure 3 ] shows a cross-sectional view of a substrate having a pixel division layer, which is listed as a specific example of an embodiment of the present invention, in which layer (B) is configured in a manner covering the entire surface of layer (A) and layer (A) and layer (B) have the same opening width.
[0029] [ Figure 4 ] shows a cross-sectional view of a substrate having a pixel dividing layer formed thereon, in which a layer (B) is arranged on a part of the surface of a layer (A) and has a spacer function, as a specific example of an embodiment of the present invention.
[0030] [ Figure 5 ] shows a cross-sectional view of a substrate having a pixel segmentation layer formed thereon and having a spacer function, which is listed as a specific example of an embodiment of the present invention, wherein layer (B) is configured to cover the entire surface of layer (A) and layer (A) and layer (B) have the same opening width.
[0031] [ Figure 6 ] shows a cross-sectional view of a substrate having a pixel segmentation layer formed thereon and having a spacer function, which is listed as a specific example of an embodiment of the present invention, wherein layer (B) is configured to cover the entire surface of layer (A) and layer (A) and layer (B) have the same opening width.
[0032] [ Figure 7 ] shows a cross-sectional view of a substrate having a pixel segmentation layer formed thereon and having a spacer function, which is listed as a specific example of an embodiment of the present invention, wherein layer (B) is arranged in a manner to cover the surface of layer (A) except for the inclined portion of the pattern periphery located at the opening portion of layer (A), and layer (A) is a layer arranged on the surface of the first electrode and the surface of the planarization layer.
[0033] [ Figure 8 ] shows a specific example of an embodiment of the present invention, in which a display unit has an opening area of 30.0 to 260.0 μm where light-emitting pixels are arranged. 2 A layer (A) having a hole pattern opening within a range of.
[0034] [ Fig. 9 ] shows a specific example of an embodiment of the present invention, in which a display unit has an opening area of 30.0 to 260.0 μm where light-emitting pixels are arranged. 2 A layer (A) having square pattern openings within a range of .
[0035] [ Fig.10 ] shows an example of layer (A), a light-emitting portion, and a non-light-emitting portion when observing a light-emitting pixel portion.
[0036] [ Fig.11 ] shows the production process of an organic EL display device including the process of forming a pixel division layer in all the embodiments and comparative examples. DETAILED DESCRIPTION
[0037] Hereinafter, the present invention will be described in detail. The numerical range represented by "~" refers to a range including the numerical values recorded before and after "~" as the lower limit and the upper limit. The so-called pixel division layer refers to the pixel division layer possessed by the organic EL display device, and does not include the black matrix of the liquid crystal display device. The so-called visible light refers to the light in the region of wavelength greater than 380nm and less than 780nm, and the so-called near ultraviolet light refers to the light in the region of greater than 200nm and less than 380nm. The so-called light shielding refers to the function of reducing the intensity of the transmitted light compared to the intensity of the light incident in the direction perpendicular to the cured film, and the so-called light shielding refers to the degree of shielding visible light. The so-called photosensitive composition refers to a composition having photosensitivity to near ultraviolet light. The so-called weight-average molecular weight (Mw) refers to the value obtained by analyzing the gel permeation chromatography with tetrahydrofuran as the carrier, using the standard curve made of standard polystyrene and converting. The so-called solid content refers to the proportion (weight %) of the components other than the solvent and water in the photosensitive composition.
[0038] "CI" used in the names of some coloring materials is the abbreviation of Colour Index Generic Name, which is based on the Colour Index published by The Society of Dyers and Colourists. For coloring materials registered in the Colour Index, the Colour Index Generic Name indicates the chemical structure and crystal form of the pigment or dye.
[0039] The inventors of the present application have verified the above-mentioned subject, and found that when a negative photosensitive composition containing a pigment and / or a dye, a compound having two or more ethylenically unsaturated double bond groups in the molecule, and a photopolymerization initiator is used to form an opening with a narrow opening width (for example, a square with a vertical width of 7.0 μm and a horizontal width of 7.0 μm), the luminescence reliability of the organic EL display device finally obtained is poor compared with the case where an opening with a large opening width is formed (for example, a square with a vertical width of 30.0 μm and a horizontal width of 30.0 μm). That is, it was found that even if the same negative photosensitive composition is used, the smaller the size of the luminescent pixel determined by the opening width of the opening of the pixel division layer, the easier it is for the luminescence reliability of the organic EL display device to decrease, and there is a mutually restrictive relationship when the display portion is made more precise.
[0040] In view of the above, the inventors of the present application conducted intensive research and came up with the idea of combining a layer containing a cured product of a negative photosensitive composition with a layer containing a cured product of a positive photosensitive composition, and found that the following configuration has a particularly significant effect in solving the above-mentioned problems.
[0041] That is, the present invention is an organic EL display device, which is an organic EL display device that includes a substrate, a planarization layer, a first electrode, a pixel division layer, a light-emitting pixel, and a second electrode in sequence, wherein the pixel division layer includes a layer (A) and a layer (B), wherein the layer (A) is a layer arranged on the surface of the first electrode in a manner that partially exposes the surface of the first electrode, and the layer (B) is a layer arranged on at least a portion of the surface of the layer (A), wherein the layer (A) contains a cured product of a negative photosensitive composition (a), wherein the negative photosensitive composition (a) contains: a pigment and / or a dye; a compound having two or more ethylenically unsaturated double bond groups in the molecule; and a photopolymerization initiator, and the layer (B) contains a cured product of a positive photosensitive composition (b), wherein the positive photosensitive composition (b) contains a resin and a photoacid generator.
[0042] The organic EL display device of the present invention includes a substrate, a planarization layer, a first electrode, a pixel division layer, a light-emitting pixel, and a second electrode in this order.
[0043] Figure 1 Detailed description of the invention is given in FIG. 4 , which is a cross-sectional view of a TFT substrate in an organic EL display device cited as a specific example of an embodiment of the present invention.
[0044] On the surface of the substrate 6, bottom-gate or top-gate TFTs 1 (thin film transistors) are arranged in rows and columns, and a TFT insulating layer 3 is formed in a state of covering the TFTs 1 and the wiring 2 connected to the TFTs 1. As TFTs 1, for example, TFTs containing oxide semiconductors such as In-Ga-Zn-O (IGZO), Ga-Zn-Sn, and low-temperature polycrystalline silicon (LTPS) can be cited. In addition, a planarization layer 4 is formed on the surface of the TFT insulating layer 3, and a contact hole 7 for opening the wiring 2 is provided in the planarization layer 4. The contact hole 7 can be, for example, a circular opening. On the surface of the planarization layer 4, a pattern of the first electrode 5 is formed and connected to the wiring 2. Layer (A) 8 is arranged on the surface of the first electrode 5 in a manner that partially exposes the surface of the first electrode 5, and layer (B) 9 is arranged on a portion of the surface of layer (A) 8, and layer (A) 8 and layer (B) 9 constitute a pixel division layer 10. The pixel division layer 10 is provided with an opening, and a light-emitting pixel 11 including an organic EL light-emitting material is formed in the opening, and the second electrode 12 is arranged in a manner of covering the layer (A) 8, the layer (B) 9 and the light-emitting pixel 11. The shape of the opening of the pixel division layer 10 is not particularly limited, and may be a square, a rectangle, a perfect circle or an ellipse, and the size of the light-emitting pixel 11 is determined by the opening width of the opening of the layer (A) 8 included in the pixel division layer 10.
[0045] When a voltage is applied to a light-emitting pixel portion after the TFT substrate having the above-described stacked structure is sealed in a vacuum, light can be emitted as an organic EL display device.
[0046] The organic EL display device of the present invention can be a bottom-emitting organic EL display device that extracts the emitted light from the light-emitting pixel 11 to the substrate side via the substrate 6, or it can be a top-emitting organic EL display device that extracts the emitted light to the opposite side of the substrate 6 via the second electrode 12, without any special limitation.
[0047] If a hard plate-like substrate represented by glass is used as the substrate 6, a rigid type organic EL display device that cannot be bent can be made. As glass, an alkali-free glass having an alkali metal content of less than 0.5% and silicon as the main component can be preferably used. Among them, glass with a small thermal expansion coefficient and excellent dimensional stability in a high-temperature process of more than 250°C is preferred, for example, OA-10G, OA-11 (all of the above are made by Nippon Electric Glass Co., Ltd.), AN-100 (made by Asahi Glass Co., Ltd.) can be cited. From the perspective of physical durability, its thickness is usually 0.1 to 0.5 mm.
[0048] On the other hand, if a flexible substrate is used, a flexible type organic EL display device can be made. As a flexible substrate, a substrate formed of a polyimide resin with high bendability and excellent mechanical strength can be preferably used. As a method for making it, the following method can be cited: a solution containing polyamic acid is applied to the surface of a temporary support, followed by heating, thereby imidizing the polyamic acid, and after converting it into a polyimide resin, the temporary support is peeled off by laser or the like. Polyamic acid can be synthesized by reacting tetracarboxylic dianhydride with a diamine compound in an amide solvent such as N-methyl-2-pyrrolidone, wherein, from the perspective of having a small thermal linear expansion coefficient and excellent dimensional stability, a polyamic acid having a residue of an aromatic tetracarboxylic dianhydride and a residue of an aromatic diamine compound is preferably used. As a specific example, a polyamic acid having a residue of 3,3',4,4'-biphenyltetracarboxylic dianhydride and a residue of p-phenylenediamine can be cited. Its thickness is usually 10 to 40 μm, which can reduce the thickness of the substrate 6 compared to the case of using the aforementioned alkali-free glass.
[0049] The planarization layer 4 is not particularly limited as long as it functions as an insulating layer configured as a base layer of the first electrode 5, and may be a layer formed in a manner to cover the convex portion generated by the thickness of the TFT 1 and to function to form a pattern of the first electrode 5 more smoothly. The planarization layer 4 may be patterned using, for example, the same photosensitive composition as the negative photosensitive composition (a) or the positive photosensitive composition (b) described later, and the planarization layer 4 may be formed of a single layer or two or more layers.
[0050] The first electrode 5 can be formed of any material as long as it is a film that functions as an anode. As the first electrode 5, for example, conductive metal oxides such as ITO (Indium Tin Oxide), ITZO (Indium Tin Zinc Oxide), and IZO (Indium Zinc Oxide) can be used. Among them, ITO can be preferably used in terms of excellent transparency and conductivity. As a method for forming an ITO pattern, the following method can be cited: first, after forming an ITO film on the entire surface by sputtering, a positive resist material for etching is formed into a pattern by photolithography to obtain a resist pattern on the ITO film. Next, an etching solution with a liquid temperature of 20 to 60°C is used to remove only the ITO film in the non-formed part of the resist pattern, and then the resist pattern is removed by a resist stripping solution with a liquid temperature of 20 to 60°C, and further heat-treated in a manner to obtain the desired crystallinity as needed. The so-called ITO here includes the so-called amorphous ITO. As a positive resist material for etching, a positive photosensitive composition containing an alkali-soluble Novolac resin can be used. As an etching solution, an aqueous solution containing nitric acid and hydrochloric acid, an aqueous solution of oxalic acid can be used. As commercially available products, for example, ITO-101N (manufactured by Kanto Chemical Co., Ltd.), "S-Clean" (registered trademark) IS-2, S-Clean IS-3 (all of the above are manufactured by SASAKI CHEMICAL CO., LTD.) can be cited.
[0051] As the resist stripping solution, an organic amine aqueous solution can be used, and commercially available products include, for example, "UNLAST (Japanese: アンラスト)" (registered trademark) M6, UNLAST M6B, UNLAST TN-1-5, and UNLAST M71-2 (all of the above are from Sanwa Junyao Research Institute). When the organic EL display device of the present invention is a top-emitting organic EL display device, in order to improve the light extraction efficiency and thus improve the luminous brightness, the first electrode 5 is preferably a laminated film obtained by laminating a transparent conductive layer on the surface of the metal reflective layer, for example, a laminated structure of silver alloy / ITO, or ITO / silver alloy / ITO. As silver alloys, for example, alloys of Ag and Cu, and alloys of Ag, Pd, and Cu can be cited.
[0052] The luminescent pixel 11 is not particularly limited, and the emitted light may have any peak wavelength. As an organic EL luminescent material constituting the luminescent pixel 11, a material obtained by further combining a hole transport layer and / or an electron transport layer in addition to the luminescent layer can be preferably used. As luminescent pixels of various colors, for example, red luminescent pixels with a peak wavelength of 560 to 700 nm, blue luminescent pixels with a peak wavelength of 420 to 490 nm, and green luminescent pixels with a peak wavelength of 500 to 550 nm can be cited. The luminescent pixel 11 may also have a tandem luminescent layer formed by stacking a plurality of luminescent layers with different peak wavelengths. As a tandem luminescent layer, for example, a white luminescent pixel formed by stacking a total of 4 luminescent layers of blue, yellow-green, red and blue in sequence can be cited. As a method for forming a pattern of the luminescent pixel 11, a mask evaporation method can be cited. The so-called mask evaporation method is a method of patterning by evaporating an organic compound using an evaporation mask. Specifically, a method of contacting an evaporation mask having an opening of a desired pattern shape for evaporation can be cited. As an example of a vapor deposition mask that can be used to form high-definition light-emitting pixels 11, there can be cited the vapor deposition mask disclosed in Japanese Patent Application Publication No. 2019-163543.
[0053] The second electrode 12 can be formed of any material as long as it is a film that functions as a cathode. As the second electrode 12, in the case where the organic EL display device of the present invention is a top-emitting organic EL display device, a layer formed of an alloy of silver and magnesium can be preferably used from the perspective of high light transmittance and excellent light extraction efficiency. It is preferred to form a thin film in a manner that becomes a layer with a higher light transmittance in the visible region than the aforementioned first electrode 5. On the other hand, in the case where the organic EL display device of the present invention is a bottom-emitting organic EL display device, it is preferred to use a layer formed of an aluminum alloy, preferably forming a thick film in a manner that becomes a layer with a higher light reflectivity in the visible region than the aforementioned first electrode 5 from the perspective of high light reflectivity and excellent light extraction efficiency. The second electrode 12 can be formed by forming a film on the entire surface using a sputtering method.
[0054] The organic EL display device of the present invention may further include a color filter substrate formed of a color filter of at least one color and a substrate. Specifically, the color filter substrate may include a color filter substrate having a cross section shown in FIG. Figure 1 The light extraction side of the TFT substrate in the organic EL display device is bonded with a cross section thereof as shown in Figure 2 By providing a color filter, the light resistance to light in the near-ultraviolet to visible light region can be improved, and the light emission reliability can be improved, especially when used outdoors.
[0055] It should be noted that the so-called light extraction side is the light-emitting surface side of the organic EL display device. If the organic EL display device is a bottom-emitting organic EL display device that extracts the emitted light from the light-emitting pixel 11 to the substrate side via the substrate 6, the light extraction side is the substrate side. If the organic EL display device is a top-emitting organic EL display device that extracts the emitted light to the opposite side of the substrate 6 via the second electrode 12, the light extraction side is the opposite side of the substrate 6.
[0056] That is, the organic EL display device of the present invention preferably further includes a color filter on the light extraction side of the light-emitting pixel.
[0057] The openings of the black matrix 14 disposed on the surface of the substrate 13 are provided with patterns of green color filters 15, red color filters 16, and blue color filters 17. The opening width / shape of the openings of the black matrix 14 is similar to the Figure 1 The opening width / shape of the opening of the layer (A) in the color filter substrate can be the same or different. The color filter substrate can also be a highly flexible substrate that can be easily attached to the substrate using a thermosetting or near-ultraviolet curing transparent adhesive. Figure 1 The surface of the substrate 6 or the surface of the second electrode 12. As the transparent adhesive, for example, "Struct Bond" (registered trademark) (manufactured by Mitsui Chemicals, Inc.) can be cited.
[0058] The pixel division layer 10 will be described in detail as follows.
[0059] The pixel segmentation layer of the organic EL display device of the present invention comprises a layer (A) and a layer (B). The layer (A) is a layer arranged on the surface of the first electrode in a manner that the surface of the first electrode is partially exposed, and the layer (B) is a layer arranged on at least a portion of the surface of the layer (A). That is, the pixel segmentation layer of the organic EL display device of the present invention is a laminated film comprising a plurality of layers. The so-called layer (A) is a layer arranged on the surface of the first electrode in a manner that the surface of the first electrode is partially exposed, which means that the layer (A) can be a layer arranged only on the surface of the first electrode, or can also be a layer arranged on the surface of other layers other than the first electrode in addition to the surface of the first electrode. There are a variety of specific examples of the structure of the layer that serves as the base of the layer (A), and preferably, the layer (A) is a structure in which the layer is arranged on the surface of the first electrode and the surface of the planarization layer.
[0060] The structure in which the layer (B) is disposed on at least a portion of the surface of the layer (A) has the effect of improving the light emission reliability of the organic EL display device. The structure formed by laminating the layer (B) containing a cured product of the positive photosensitive composition (b) containing a resin and a photoacid generator can obtain the desired high light emission reliability regardless of the resolution of the layer (A).
[0061] The high luminescence reliability in this specification means that the area ratio of the luminescent part relative to the area of the luminescent pixel part of the organic EL display device (pixel luminescent area ratio) is maintained at a high level, that is, the generation of non-luminescent parts due to pixel shrinkage is small. The higher the luminescence reliability, the longer the luminescence life, and it can be used for a long time with high brightness, so it is valuable as a display device. There is a tendency that the smaller the luminescent pixel size, the easier it is to increase the area of the non-luminescent part that tends to move slowly from the peripheral part to the central part of the luminescent pixel part. In addition, the smaller the luminescent pixel size, the smaller the non-luminescent part per 1.0μm 2 The greater the change in pixel luminous area ratio in area.
[0062] As the mechanism for achieving the technical effect of the present invention, various factors can be considered, but it is believed that layer (B) at least contributes to the effect of allowing compounds having two or more ethylenically unsaturated double bond groups in the molecule, unreacted portions of photopolymerization initiators and / or decomposition products remaining in the cured product of the negative photosensitive composition (a) to remain inside the film of layer (A), thereby inhibiting their release into the light-emitting element.
[0063] The manner in which the pixel division layer of layer (B) is disposed on at least a portion of the surface of layer (A) is not particularly limited. Specific examples of preferred embodiments of the organic EL display device of the present invention are shown in Figure 3 to Figure 7 . These different pixel segmentation layer modes may coexist within the surface of the display portion of the organic EL display device. The display portion of the organic EL display device refers to the area where the light emitted from the luminous pixels is recognized by the user of the organic EL display device on the light extraction side when the organic EL display device is driven. There is no particular limitation on the content displayed on the display portion, and for example, text information, images or animations may be cited. On the other hand, decorative portions such as a frame portion where no luminous pixels are configured are not included in the display portion.
[0064] The pixel segmentation layer of the organic EL display device of the present invention preferably has a stepped shape and has a spacer function. By having a spacer function, when forming a light-emitting pixel, the contact area between the pixel segmentation layer and the vapor deposition mask can be reduced, and gaps and damage can be prevented, thereby improving the production yield.
[0065] From the perspective of improving luminescence reliability, the area in which layer (A) contacts layer (B), i.e., the area in which layer (B) covers layer (A), is preferably greater than 5% of the total surface area of layer (A) in the display portion of the organic EL display device, and more preferably greater than 20%.
[0066] That is, for the organic EL display device of the present invention, it is preferred that the display portion has a portion where the surface area ratio of the surface of the layer (A) covered by the layer (B) is 20 to 100% of the total surface area of the layer (A) of 100%. The surface area ratio of the layer (B) covering the layer (A) can be calculated as follows: in a square area of 250 μm in length and 250 μm in width randomly selected in the display portion, the area of the surface of the layer (A) covered by the layer (B), that is, the area of the portion where the layer (B) is arranged on the surface of the layer (A) (μm 2 ) divided by the total surface area (μm 2 ) and further multiply the obtained value by 100, and then round the obtained value to the first decimal place to calculate it.
[0067] It should be noted that the area of the region of 250 μm in length and 250 μm in width in the display portion, that is, 62500 μm 2 The value obtained by subtracting the area of the openings of the layer (A) formed in the same region of 250 μm in length and 250 μm in width in the display portion was regarded as the total surface area of the layer (A).
[0068] From the perspective of improving the effect of suppressing external light reflection and improving the luminescence reliability, the optical density of layer (A) per 1.0 μm film thickness is preferably 0.5 or more, more preferably 0.7 or more. From the perspective of improving the luminescence reliability, it is preferably 1.5 or less, more preferably 1.4 or less.
[0069] That is, the optical density (OD / μm) of the layer (A) included in the pixel division layer provided in the organic EL display device of the present invention per 1.0 μm of film thickness is preferably 0.5 to 1.5.
[0070] From the viewpoint of improving light emission reliability, the optical density (Optical Density) of the layer (B) per 1.0 μm of film thickness is preferably 0.3 or less, more preferably 0.1 or less.
[0071] That is, the optical density (OD / μm) of the layer (B) included in the pixel division layer of the organic EL display device of the present invention per 1.0 μm of film thickness is preferably 0.0 to 0.3.
[0072] The optical density per 1.0 μm film thickness here refers to the value obtained by measuring the incident light intensity and the transmitted light intensity using a densitometer (manufactured by X-Rite; X-Rite 361T" and dividing the value calculated by the following formula by the value of the film thickness, and rounding off the second decimal place. The higher the optical density, the higher the light-shielding property.
[0073] Optical density = log10 (I0 / I)
[0074] I0: incident light intensity
[0075] I: Transmitted light intensity
[0076] In the area where layer (B) is disposed on the surface of layer (A), the maximum value of the film thickness of layer (A) is preferably 0.5 μm or more, more preferably 0.8 μm or more, from the perspective of improving light-shielding properties. From the perspective of improving light-emitting reliability, it is preferably 3.0 μm or less, more preferably 2.0 μm or less.
[0077] In the portion where layer (B) is disposed on the surface of layer (A), the maximum value of the film thickness of layer (B) is preferably 0.1 μm or more, more preferably 0.3 μm or more, from the perspective of improving luminescence reliability. From the perspective of improving luminescence reliability, it is preferably 3.0 μm or less, more preferably 2.0 μm or less.
[0078] That is, for the organic EL display device of the present invention, it is preferred that, in a portion where layer (B) is arranged on the surface of layer (A), the maximum film thickness of layer (A) is 0.5 to 3.0 μm and the maximum film thickness of layer (B) is 0.1 to 3.0 μm.
[0079] The maximum value of the film thickness of layer (A) and the maximum value of the film thickness of layer (B) mentioned here can be calculated by rounding off the second decimal place of the values obtained by measuring the maximum value of the film thickness of layer (A) and the maximum value of the film thickness of layer (B) in an area of 250 μm in length and 250 μm in width randomly selected in the display part of the organic EL display device.
[0080] For the film thickness of layer (A) and layer (B), a scanning electron microscope (hereinafter referred to as "SEM") can be used to observe the cross section of the pixel segmentation layer, and the images taken can be measured separately. In the case where the two layers are mixed or fused to form an intermediate layer in the surface where layer (A) and layer (B) are in contact, the center of the film depth direction corresponding to the intermediate layer can be regarded as the interface between layer (A) and layer (B) to measure the film thickness separately. As a method other than SEM, a method using a stylus film thickness measuring device can be cited.
[0081] From the perspective of improving the film-forming property of the second electrode and suppressing the non-lighting of the luminous pixel, the cross-sectional cone angle of the end of the pixel segmentation layer at the boundary with the opening of the pixel segmentation layer is preferably 50° or less, and more preferably 40° or less. From the perspective of improving the light-shielding property of the end of the opening of the pixel segmentation layer, it is preferably 15° or more, and more preferably 20° or more. In addition, from the same point of view, it is preferred that the two layers are configured in such a way that the opening width of the opening of the layer (A) is the same as or narrower than the opening width of the opening of the layer (B). That is, it is preferred that the end of the opening of the pixel segmentation layer has light-shielding properties from the layer (A).
[0082] In the organic EL display device, from the viewpoint of improving the light emission reliability, it is preferred that the layer (A) has an opening area of 30.0 μm where light emitting pixels are arranged in the display portion. 2 In addition, from the perspective of increasing the number of light-emitting pixels that can be arranged per unit area and improving display quality, it is preferred that the opening area where the light-emitting pixels are arranged is 260.0 μm. 2 The following opening.
[0083] That is, in the organic EL display device of the present invention, it is preferred that the layer (A) has an opening area of 30.0 to 260.0 μm in which light-emitting pixels are arranged in the display portion. 2 The opening of the
[0084] The shape of each opening is not particularly limited, and may be, for example, a perfect circular opening with a diameter of 7 to 18 μm or a square opening with a side of 6 to 16 μm. The smaller the area of each luminescent pixel, the more significant the excellent technical effect of the present invention, such as high luminescent reliability, becomes.
[0085] As a specific example of the embodiment of the present invention, a display unit having an opening area of 30.0 to 260.0 μm where light-emitting pixels are arranged is provided. 2 The range of the hole pattern opening layer (A) is shown in Figure 8 , the opening area of the light-emitting pixel is 30.0 to 260.0 μm 2 The layer (A) of the square pattern openings within the range is shown in Fig. 9 .
[0086] Layer (A) contains a cured product of a negative photosensitive composition (a) as an essential component, wherein the negative photosensitive composition (a) contains: a pigment and / or a dye; a compound having two or more ethylenically unsaturated double bond groups in the molecule; and a photopolymerization initiator. A film containing a cured product is sometimes referred to as a cured film. From the perspective of improving the reliability of light emission, the content of the cured product of the negative photosensitive composition (a) is preferably 99% by weight or more in layer (A). The so-called negative photosensitive composition refers to a composition having negative photosensitivity, that is, the alkali solubility of the film in the exposed portion is relatively low compared to the alkali solubility of the film in the unexposed portion by pattern exposure through a negative exposure mask, thereby removing the film in the unexposed portion using an alkaline developer to form a pattern.
[0087] Layer (B) contains a cured product of a positive photosensitive composition (b) as an essential component, wherein the positive photosensitive composition (b) contains a resin and a photoacid generator. A film containing a cured product is sometimes referred to as a cured film. From the perspective of improving luminescence reliability, the content of the cured product of the positive photosensitive composition (b) is preferably 99% by weight or more in layer (B). The so-called positive photosensitive composition refers to a composition having positive photosensitivity, that is, by pattern exposure through a positive exposure mask, the alkali solubility of the film in the exposed portion is relatively high compared to the alkali solubility of the film in the unexposed portion, thereby removing the film in the exposed portion using an alkaline developer to form a pattern.
[0088] The cured product of the negative photosensitive composition (a) as referred to herein refers to a product obtained by a method including at least a step of heating the negative photosensitive composition (a) at a heating temperature of at least 200° C. for 10 minutes or more. The cured product of the positive photosensitive composition (b) refers to a product obtained by a method including at least a step of heating the positive photosensitive composition (b) at a temperature of at least 200° C. for 10 minutes or more.
[0089] Layer (A) contains a cured product of a negative photosensitive composition (a) as an essential component, and layer (B) contains a cured product of a positive photosensitive composition (b) as an essential component, but each may contain other components within the scope of not impairing the technical effect of the present invention. As other components, for example, water adsorbed on the cured product of the negative photosensitive composition (a) or the cured product of the positive photosensitive composition (b) can be cited. The total amount of other components is preferably 1% by weight or less in each of layer (A) and layer (B).
[0090] The negative photosensitive composition (a) contains a pigment and / or a dye. By containing a pigment and / or a dye, it is possible to impart light-shielding properties to layer (A). As the pigment, a benzodifuranone-based black pigment is preferred from the perspective of excellent light-shielding properties and luminescence reliability. The so-called benzodifuranone-based black pigment is an organic black pigment formed by a compound having a polycyclic structure in which two furanone rings are fused on one benzene ring in the molecule, and an example thereof is bis-oxoindoleyl-benzodifuranone described in International Publication No. 2009 / 010521. Among them, from the perspective of improving luminescence reliability, the cured product of the negative photosensitive composition (a) preferably contains a benzodifuranone-based black pigment represented by formula (1) or formula (2). The cured product of the negative photosensitive composition (a) more preferably contains a benzodifuranone-based black pigment represented by formula (3). With respect to formula (3), R in formula (1) 1 ~R 10 is a hydrogen atom. Commercially available products of the benzodifuranone-based black pigment represented by formula (3) include Irgaphor Black (registered trademark) S0100CF and Experimental Black 582 (all of the above are manufactured by BASF). From the perspective of improving the resolution of layer (A), for the benzodifuranone-based black pigment represented by formula (1) or formula (2), it is preferred that at least a portion of the pigment surface is coated with a coating layer comprising silicon dioxide, a metal oxide and / or a metal hydroxide. From the perspective of improving the resolution of layer (A), the cured product of the negative photosensitive composition (a) more preferably further contains a compound represented by formula (4) or a salt thereof. By pre-adding the benzodifuranone-based black pigment represented by formula (1) or formula (2) to the negative photosensitive composition (a), the cured product of the negative photosensitive composition (a) can contain the benzodifuranone-based black pigment represented by formula (1) or formula (2).
[0091] [Chemical formula 1]
[0092]
[0093] [Chemical formula 2]
[0094]
[0095] In formula (1) and formula (2), R 1 ~R 10 Each independently represents a hydrogen atom, a fluorine atom, an alkyl group having 1 to 12 carbon atoms, a hydroxyl group or a carboxyl group.
[0096] [Chemical formula 3]
[0097]
[0098] [Chemical formula 4]
[0099]
[0100] From the perspective of improving light emission reliability, the cured product of the negative photosensitive composition (a) preferably contains at least one perylene organic pigment selected from the group consisting of CI Pigment Red 123, CI Pigment Red 149, CI Pigment Red 178, CI Pigment Red 179, CI Pigment Red 190, CI Pigment Violet 29 and 3,4,9,10-perylenetetracarboxylic acid bisbenzimidazole. More preferably, it contains 3,4,9,10-perylenetetracarboxylic acid bisbenzimidazole.
[0101] That is, the cured product of the negative photosensitive composition (a) contained in the layer (A) provided in the organic EL display device of the present invention more preferably further contains bisbenzimidazole-3,4,9,10-perylenetetracarboxylate.
[0102] The term "3,4,9,10-perylenetetracarboxylic acid bisbenzimidazole" as used herein includes the compound represented by the formula (5) as a cis isomer and the compound represented by the formula (6) as a trans isomer.
[0103] [Chemical formula 5]
[0104]
[0105] By allowing the negative photosensitive composition (a) to contain the above-mentioned perylene-based organic pigment in advance, the above-mentioned perylene-based organic pigment can be contained in the cured product of the negative photosensitive composition (a).
[0106] As other pigments, for example, organic pigments such as CI Pigment Yellow 151, 175, 180, 185, 192, CI Pigment Red 254, 255, 264, CI Pigment Orange 43, 61, 72, CI Pigment Blue 15:3, 15:4, 15:6, 25, 26, 60, 65, 80, CI Pigment Violet 19, 29, 32, 37, and inorganic pigments such as carbon black, titanium nitride, and zirconium nitride may be used in combination.
[0107] As dyes, oil-soluble dyes and acid dyes are preferred from the viewpoint of solubility in solvents and developability, and examples thereof include red dyes such as CI Solvent Red 46, 72, CI Acid Red 52, 87, 289, and 388, yellow dyes such as CI Solvent Yellow 93, blue dyes such as CI Solvent Blue 35, 45, 97, 104, 122, CI Acid Blue 9, 25, 27, 40, 80, 90, 112, 127, 129, and 145, violet dyes such as CI Solvent Violet 9, 13, 43, CI Acid Violet 29, 31, 33, 36, 39, 48, 63, and 109, and black dyes such as CI Solvent Black 27, 29, 34, and CI Acid Black 52. If necessary, the acid dye may be salted with a basic dye or a cationic component to improve the solubility in a solvent.
[0108] The negative photosensitive composition (a) may contain pigments and dyes, and the total content of these pigments and dyes is preferably 10 to 50% by weight of the solid content of 100% by weight of the negative photosensitive composition in order to achieve both light-shielding properties and resolution of the layer (A). The aforementioned organic pigments and dyes have near-infrared transmittance, and can use a near-infrared camera to perform high-precision automatic alignment, i.e., near-infrared alignment, between the substrate formed with the prebaked film and the exposure mask, thereby improving the yield rate when producing panels.
[0109] The negative photosensitive composition (a) contains a compound having two or more ethylenically unsaturated double bond groups in the molecule. The compound having two or more ethylenically unsaturated double bond groups in the molecule has the effect of causing the photocuring reaction to proceed in a chain reaction by utilizing the free radical active species generated by the photopolymerization initiator described later, making the alkali solubility of the film of the exposed part relatively low compared to the alkali solubility of the film of the unexposed part, and can form a pattern by negative photolithography. Specific examples include "KAYARAD" (registered trademark) DPHA, KAYARAD DPCA-20, KAYARAD DPCA-30, KAYARAD DPCA-60, KAYARAD DPCA-120, KAYARAD ZAR-1494H, KAYARAD ZAR-2001H, KAYARAD ZFR-1491H, KAYARAD ZCR-1569H, KAYARAD ZCR-1797H, KAYARAD ZCR-1798H, KAYARAD ZCR-1761H, CCR-1171H, CCR-1291H, CCR-1307H, CCR-1309H (all manufactured by Nippon Kayaku Co., Ltd.), "LIGHT ACRYLATE" (registered trademark) BP-4EAL, LIGHT ACRYLATE BP-4PA (all of the above are manufactured by Kyoeisha Chemical Co., Ltd.), "OGSOL" (registered trademark) EA-0200, OGSOL EA-0250P, OGSOL EA-0300, OGSOL CR-1030 (all of the above are manufactured by Osaka Gas Chemicals Co., Ltd.), an alkali-soluble epoxy acrylate resin containing an unsaturated double bond group having a structural unit represented by formula (7), and an alkali-soluble polyimide precursor containing an unsaturated double bond group having a structural unit represented by formula (8). They can be used alone or in combination. It should be noted that the compound having two or more ethylenically unsaturated double bond groups in the molecule and corresponding to the alkali-soluble resin described later is defined as a component of a compound having two or more ethylenically unsaturated double bond groups in the molecule.
[0110] From the viewpoint of achieving both film adhesion and resolution in the development step, the content of the compound having two or more ethylenically unsaturated double bond groups in the molecule is preferably 10 to 60% by weight based on 100% by weight of the solid content of the negative photosensitive composition.
[0111] [Chemical formula 6]
[0112]
[0113] In formula (7), R 34 , R35 Each independently represents a hydrogen atom or a methyl group. * represents a bonding site to a carbon atom.
[0114] [Chemical formula 7]
[0115]
[0116] In formula (8), R 36 represents a tetravalent organic group containing an aromatic ring or a cycloaliphatic ring. 37 represents a trivalent organic group containing an aromatic ring or a cyclic aliphatic ring. 38 represents an alkylene group having 1 to 5 carbon atoms. 39 represents a hydrogen atom or a methyl group. * represents a bonding site.
[0117] The negative photosensitive composition (a) contains a photopolymerization initiator. The photopolymerization initiator is not particularly limited as long as it is a compound that generates free radical active species by exposure to near ultraviolet light. As the photopolymerization initiator, for example, oxime ester photopolymerization initiators, alkyl phenone photopolymerization initiators, and acylphosphine oxide photopolymerization initiators can be mentioned. Among them, from the perspective of improving the adhesion of the film in the development process, oxime ester photopolymerization initiators are preferred, for example, "Adeka Arkls" (registered trademark) NCI-831E, Ade ka Arkls N-1919T (all of the above are made by ADEKA (Co., Ltd.)), "Irgacure" (registered trademark) OXE01, Irgacure OXE02, Irgacure OXE03, Irgacure OXE04, and the compound represented by formula (9) can be mentioned. From the viewpoint of achieving both film adhesion and resolution in the development step, the content of the photopolymerization initiator is preferably 1 to 10% by weight based on 100% by weight of the solid content of the negative photosensitive composition.
[0118] [Chemical formula 8]
[0119]
[0120] From the perspective of improving the resolution of layer (A), the negative photosensitive composition (a) preferably further contains an alkali-soluble resin. The alkali-soluble resin herein refers to the following resin: a solution obtained by dissolving the resin in γ-butyrolactone is applied to the surface of a silicon wafer, and pre-baked for 4 minutes on a hot plate at an actual temperature of 120°C to form a pre-baked film with a film thickness of 10±0.5μm, and the pre-baked film is immersed in a 2.38 wt% tetramethylammonium hydroxide aqueous solution at 23±1°C as an alkaline developer for 1 minute, and then rinsed with pure water at 23±1°C for 10 seconds, and the dissolution rate in the film depth direction obtained from the film reduction is a resin of 50nm / minute or more. The so-called resin refers to a compound having a weight average molecular weight (Mw) of 1000 or more and having a polymer chain containing repeating structural units.
[0121] As the alkali-soluble resin, for example, alkali-soluble phenolic resin, alkali-soluble (meth) acrylic resin, alkali-soluble polyhydroxystyrene, alkali-soluble polyimide, alkali-soluble polyimide precursor, alkali-soluble polybenzoxazole, alkali-soluble polybenzoxazole precursor, alkali-soluble polysiloxane, alkali-soluble polyamine can be mentioned. They can be used alone or in combination. The so-called alkali-soluble polyimide precursor here refers to a resin that forms an imide bond and is converted into a polyimide by heat treatment. As a specific example, polyamic acid and polyamic acid ester can be mentioned.
[0122] Among them, from the perspective of reducing the cross-sectional cone angle of the end of layer (A) and improving the resolution, it is preferred to contain an alkali-soluble phenolic resin, an alkali-soluble (meth) acrylic resin and / or an alkali-soluble polyimide. In addition, as a pigment dispersant, it is preferred to contain an alkali-soluble polyamine. The so-called (meth) acrylic resin refers to a methacrylic resin or an acrylic resin. As an alkali-soluble phenolic resin, for example, in addition to Novolac-type phenolic resin and Resol-type phenolic resin, the Novolac-type phenolic resin having a polymer chain containing polyhydroxystyrene described in Japanese Patent Application Laid-Open No. 2010-106278 can also be cited, which can be synthesized using a known method. It can be obtained by reacting aldehyde compounds such as formaldehyde and benzaldehyde with compounds having a phenol skeleton such as phenol, o-cresol, m-cresol, p-cresol, 2,5-xylenol, 3,5-xylenol, etc. in the presence of an acidic catalyst or a basic catalyst. Examples of commercially available products include TRR5030G, TRR5010G, TR4020G, TR4080G, TR4000B, TRM30B20G, and EP23F10G (all manufactured by Asahi Organic Materials Co., Ltd.).
[0123] Preferred examples of the alkali-soluble polyamine include resins having two or more tertiary amino groups in the molecule described in Patent Document 1. Examples of the alkali-soluble polyimide include resins having a structural unit represented by the formula (10) described below.
[0124] The negative photosensitive composition (a) may further contain a solvent. By containing a solvent, the viscosity and thixotropy of the negative photosensitive composition can be adjusted, and the uniformity of the film thickness of the coating film can be improved. As a solvent, for example, preferably propylene glycol monomethyl ether (hereinafter, expressed as PGME), propylene glycol monoethyl ether, dipropylene glycol monomethyl ether, propylene glycol monomethyl ether acetate (hereinafter, expressed as "PGMEA"), 3-methoxybutyl acetate (hereinafter, expressed as "MBA"), methyl lactate, ethyl lactate, γ-butyrolactone, valerolactone, ε-caprolactone. From the viewpoint of storage stability, the water content in 100 parts by weight of the negative photosensitive composition (a) is preferably 0.01 to 0.5 parts by weight. From the perspective of obtaining a higher uniformity of film thickness, a leveling agent containing a nonionic surfactant may be contained.
[0125] From the perspective of improving the reliability of luminescence, the cured product of the negative photosensitive composition (a) contained in the layer (A) preferably contains silica particles having a primary particle size of 5 to 30 nm and an aspect ratio (major diameter / minor diameter) of 1.0 to 1.5. The silica particles referred to herein refer to particles in which the pure SiO2 is 90% by weight or more of the weight after water is removed, particles formed of silica (anhydrous silicic acid), particles formed of silica hydrate (hydrous silicic acid, white carbon), or particles formed of quartz glass. In addition, particles formed of orthosilicic acid, metasilicic acid and / or metadisilic acid are also included. The structure of the particles is not particularly limited and may have internal voids. The aspect ratio referred to herein refers to the value obtained by rounding off the second decimal place of the value obtained by dividing the major diameter of the silica particles by the minor diameter. It should be noted that when the aspect ratio is 1.0, it can be regarded as a spherical silica particle. By allowing the negative photosensitive composition (a) to contain silica particles having a primary particle size of 5 to 30 nm and an aspect ratio (major axis / minor axis) of 1.0 to 1.5 or a dispersion containing the same in advance, the silica particles can be contained in the cured product of the negative photosensitive composition (a).
[0126] As commercial products of a dispersion of silica particles having a primary particle size of 5 to 30 nm and an aspect ratio (long diameter / short diameter) of 1.0 to 1.5, MEK-ST-40 and MEK-ST-L (all of which are manufactured by Nissan Chemical Industries, Ltd.) can be cited. For the primary particle size and aspect ratio, the product obtained by thinly cutting the pixel division layer can be used as an observation sample. For the cross section that has been polished by ion milling to improve the smoothness, a transmission electron microscope (TEM) is used to observe the portion located in the range of 0.2 to 0.8 μm from the outermost layer of the pixel division layer in the film depth direction under a magnification of 50,000 times to obtain a captured image, and the captured image is measured using an image analysis type particle size distribution measuring machine "Mac-View" (manufactured by MOUNTECH). Furthermore, the silica particles can be determined by identifying the elements constituting the particles using energy dispersive X-ray spectroscopy (TEM-EDX).
[0127] The negative photosensitive composition (a) may further contain a thermal crosslinking agent. By containing an appropriate amount of a thermal crosslinking agent within the range of not damaging the resolution, higher light emission reliability can sometimes be obtained. As a thermal crosslinking agent, a compound having two or more epoxy groups is preferred, and specific examples include TEPIC-L, TEPIC-S, TEPIC-PAS (all of which are manufactured by Nissan Chemical Industries, Ltd.), NC-3000, XD-1000, and XD-1000H (all of which are manufactured by Nippon Kayaku Co., Ltd.).
[0128] The positive photosensitive composition (b) contains a resin. The resin is not particularly limited, and examples thereof include the alkali-soluble resins described above.
[0129] From the perspective of obtaining high luminescence reliability, the cured product of the positive photosensitive composition (b) contained in layer (B) preferably contains a resin having an imide bond and / or a benzoxazole skeleton. By pre-making the positive photosensitive composition (b) contain a resin having an imide bond and / or a benzoxazole skeleton or a precursor thereof, the cured product of the positive photosensitive composition (b) can contain a resin having an imide bond and / or a benzoxazole skeleton. From the above viewpoints, among the aforementioned alkali-soluble resins, the positive photosensitive composition (b) preferably contains an alkali-soluble polyimide, an alkali-soluble polyimide precursor, an alkali-soluble polybenzoxazole, an alkali-soluble polybenzoxazole precursor and / or their copolymers. More preferably, it contains a resin having a structural unit represented by formula (10) and / or a structural unit represented by formula (11).
[0130] [Chemical formula 9]
[0131]
[0132] In formula (10), R11 represents a 4- to 10-valent organic group. 12 represents a 2- to 8-valent organic group. 13 and R 14 Each independently represents a phenolic hydroxyl group or a carboxyl group, and each may be a single group or a mixture of different groups. p and q are integers, and each independently represents 0 to 6. However, p+q>0 is satisfied. * represents a bonding site.
[0133] [Chemical formula 10]
[0134]
[0135] In formula (11), R 15 and R 16 represents a 2- to 8-valent organic group. 17 and R 18 Each independently represents a hydroxyl group, a carboxyl group or a COOA group, each of which may be a single group or a mixture of different groups. A represents a monovalent hydrocarbon group having 1 to 10 carbon atoms. r and s are integers, each independently representing 0 to 6. However, r+s>2 is satisfied. * represents a bonding site.
[0136] In the formula (11), examples of the monovalent hydrocarbon group A having 1 to 10 carbon atoms include a methyl group, an ethyl group, a propyl group, a phenyl group, and a benzyl group.
[0137] From the viewpoint of improving resolution, the weight average molecular weight (Mw) of the resin having the structural unit represented by formula (10) and / or the structural unit represented by formula (11) is preferably 10,000 or more and 50,000 or less.
[0138] In formula (10), R 11 -(R 13 )p represents the residue of an acid dianhydride. 11It is preferably an organic group having 5 to 40 carbon atoms and containing an aromatic ring or a cyclic aliphatic group. Examples of the acid dianhydride residue include pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, and 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride. , bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, 1,2,5,6-naphthalenetetracarboxylic acid dianhydride, 2,3,6,7-naphthalenetetracarboxylic acid dianhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, 9,9-bis{4-(3,4-dicarboxyphenoxy)phenyl}fluorene dianhydride, and the acid dianhydride having the structure represented by formula (12); and residues of aromatic tetracarboxylic acid dianhydrides such as butanetetracarboxylic acid dianhydride and the residue of aliphatic tetracarboxylic acid dianhydride such as butanetetracarboxylic acid dianhydride and the residue of 1,2,3,4-cyclopentanetetracarboxylic acid dianhydride.
[0139] [Chemical formula 11]
[0140]
[0141] In formula (12), R 19 represents a single bond, an oxygen atom, C(CF3)2, C(CH3)2 or SO2. 20 and R 21 Each independently represents a hydrogen atom or a hydroxyl group.
[0142] In formula (11), R 15 -(R 17 )r represents an acid residue. 15 It is preferably an organic group having 5 to 40 carbon atoms and containing an aromatic ring or a cyclic aliphatic group.
[0143] Examples of the acid residue include dicarboxylic acid residues, tricarboxylic acid residues, and tetracarboxylic acid residues. Examples of dicarboxylic acids include terephthalic acid, isophthalic acid, diphenyl ether dicarboxylic acid, bis(carboxyphenyl)hexafluoropropane, biphenyl dicarboxylic acid, benzophenone dicarboxylic acid, and triphenyl dicarboxylic acid. Examples of tricarboxylic acids include trimellitic acid, trimesic acid, diphenyl ether tricarboxylic acid, and biphenyl trimaric acid residues. Examples of the tetracarboxylic acid residue include pyromellitic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 2,3,3',4'-biphenyltetracarboxylic acid, 2,2',3,3'-biphenyltetracarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 2,2',3,3'-benzophenonetetracarboxylic acid, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane, 2,2-bis(2,3-dicarboxyphenyl)hexafluoropropane, 1,1-bis(3,4-dicarboxyphenyl)ethane, Residues of aromatic tetracarboxylic acids such as the residues of 1,1-bis(2,3-dicarboxyphenyl)ethane, bis(3,4-dicarboxyphenyl)methane, bis(2,3-dicarboxyphenyl)methane, bis(3,4-dicarboxyphenyl)ether, 1,2,5,6-naphthalenetetracarboxylic acid, 2,3,6,7-naphthalenetetracarboxylic acid, 2,3,5,6-pyridinetetracarboxylic acid, and 3,4,9,10-perylenetetracarboxylic acid; and residues of aliphatic tetracarboxylic acids such as the residues of butanetetracarboxylic acid and 1,2,3,4-cyclopentanetetracarboxylic acid.
[0144] R in formula (10) 12 -(R 14 )q and R in formula (11) 16 -(R 18 )s represents a diamine residue. 12 and R 16 It is preferably an organic group having 5 to 40 carbon atoms and containing an aromatic ring or a cyclic aliphatic group.
[0145] Examples of the diamine residue include 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 1,4-bis(4-aminophenoxy)benzene, m-phenylenediamine, p-phenylenediamine, 1,5-naphthalenediamine, 2,6-naphthalenediamine, bis(4-aminophenoxy)biphenyl, bis{4-(4-aminophenoxy)phenyl}ether, 1,4-bis(4-aminophenoxy)benzene, 2,2'-dimethyl-4,4'-diamine. The residues of aminobiphenyl, 2,2'-diethyl-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diethyl-4,4'-diaminobiphenyl, 9-bis(4-aminophenyl)fluorene, or the residues of compounds obtained by replacing at least a part of the hydrogen atoms in the aromatic rings of these compounds with alkyl groups or halogen atoms, and the residues of compounds represented by formula (13), compounds represented by formula (14), compounds represented by formula (15), and compounds represented by formula (16).
[0146] [Chemical formula 12]
[0147]
[0148] In formula (13), R 22 represents a single bond, an oxygen atom, C(CF3)2, C(CH3)2 or SO2. 23 and R 24 Each independently represents a hydrogen atom or a hydroxyl group.
[0149] [Chemical formula 13]
[0150]
[0151] In formula (14), R 25 represents a single bond, an oxygen atom, C(CF3)2, C(CH3)2 or SO2. 26 and R 27 Each independently represents a hydrogen atom or a hydroxyl group.
[0152] [Chemical formula 14]
[0153]
[0154] In formula (15), R 28 , R 29 , R 30 and R 31 Each independently represents a hydrogen atom or a hydroxyl group.
[0155] [Chemical formula 15]
[0156]
[0157] In formula (16), R 32 and R 33 Each independently represents a hydrogen atom or a hydroxyl group.
[0158] Furthermore, by blocking the terminals of these resins with monoamines, it is possible to easily adjust the weight average molecular weight (Mw) during synthesis and improve the storage stability as an alkali-soluble resin.
[0159] Examples of the monoamine include 1-hydroxy-4-aminonaphthalene, 2-hydroxy-7-aminonaphthalene, 2-hydroxy-6-aminonaphthalene, 2-hydroxy-5-aminonaphthalene, 1-carboxy-7-aminonaphthalene, 1-carboxy-6-aminonaphthalene, 1-carboxy-5-aminonaphthalene, 2-carboxy-7-aminonaphthalene, 2-carboxy-6-aminonaphthalene, 2-aminophenol, 3-aminophenol and 4-aminophenol.
[0160] In formula (11), the group represented by COOA can be obtained by converting a carboxyl group using an esterifying agent. Examples of the esterifying agent include N,N-dimethylformamide dimethyl acetal and N,N-dimethylformamide diethyl acetal.
[0161] A resin having a structural unit represented by formula (10) and / or a structural unit represented by formula (11) can be obtained by a known method, for example, it can be synthesized by the method disclosed in Japanese Patent No. 4341293, International Publication No. 2014 / 097992, and International Publication No. 2019 / 181782.
[0162] From the viewpoint of improving light emission reliability, the content of the resin is preferably 50 to 90 wt % based on 100 wt % of the solid content of the positive photosensitive composition (b).
[0163] The positive photosensitive composition (b) contains a photoacid generator. The photoacid generator is not particularly limited as long as it is a compound that decomposes and generates an acid by irradiation with near-ultraviolet light. The generated acid makes the alkali solubility of the film in the exposed part relatively higher than the alkali solubility of the film in the unexposed part, and a pattern can be formed by positive photolithography. Examples of the generated acid include indene carboxylic acid, methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and naphthalenesulfonic acid.
[0164] As a photoacid generator, for example, quinonediazide compounds, imide sulfonate compounds, and oxime sulfonate compounds can be cited. Among them, from the perspective of improving the reliability of luminescence, it is preferred that a quinonediazide compound that generates carboxylic acid and / or sulfonic acid as an acid by irradiation with near-ultraviolet light. As a quinonediazide compound, there can be cited: a diazide naphthoquinone-4-sulfonate compound as a compound obtained by an esterification reaction of a compound having a phenolic hydroxyl group with 1,2-naphthoquinone-2-diazide-4-sulfonyl chloride (hereinafter, sometimes referred to as "diazido naphthoquinone-4-sulfonyl chloride"); a diazide naphthoquinone-5-sulfonate compound as a compound obtained by an esterification reaction of a compound having a phenolic hydroxyl group with 1,2-naphthoquinone-2-diazide-5-sulfonyl chloride (hereinafter, sometimes referred to as "diazido naphthoquinone-5-sulfonyl chloride"); a diazide naphthoquinone sulfonic acid derivative described in Japanese Patent Application Laid-Open No. 2019-174793. Examples of the compound having a phenolic hydroxyl group include TrisP-HAP, TrisP-PA, TekP-4HBPA, TrisP-SA, TrisOCR-PA, BisP-AP, BisP-NO, BisP-PR, BisP-B, Bis P-DE, BisP-DP, BisP-DP, BisRS-2P, BisRS-3P, and BisP-DEK (all of which are manufactured by Honshu Chemical Industry Co., Ltd.). Examples of commercially available products of naphthoquinone diazide-5-sulfonate compounds include 4NT-250 and 4NT-300 (manufactured by Toyo Gosei Kogyo Co., Ltd.). From the viewpoint of improving exposure sensitivity, the content of the photoacid generator is preferably 1 to 40% by weight in 100% by weight of the solid content of the positive photosensitive composition (b).
[0165] The positive photosensitive composition (b) may further contain a thermal crosslinking agent. By containing a thermal crosslinking agent, better light emission reliability can be obtained. As the thermal crosslinking agent, a compound having two or more alkoxyalkyl groups in the molecule is preferred. As the alkoxyalkyl group, for example, methoxymethyl, ethoxymethyl, propoxymethyl, butoxymethyl can be mentioned. As the compound having two or more alkoxymethyl groups in the molecule, for example, a compound represented by formula (17), a compound represented by formula (18), and a compound represented by formula (19) can be preferably mentioned.
[0166] [Chemical formula 16]
[0167]
[0168] [Chemical formula 17]
[0169]
[0170] The positive photosensitive composition (b) may further contain the aforementioned solvent. By containing a solvent, the viscosity, thixotropy, etc. of the positive photosensitive composition can be adjusted, and the uniformity of the film thickness of the coating film can be improved.
[0171] For the organic EL display device of the present invention, within the scope of not impairing the effect of the present invention, similarly to layer (A), layer (B) may contain a pigment and / or a dye. However, from the perspective of obtaining high light emission reliability, the total content of the pigment and the dye is preferably less than 5 parts by weight in 100 parts by weight of layer (B), and more preferably 0 parts by weight.
[0172] That is, the organic EL display device of the present invention is preferably the following organic EL display device, which is an organic EL display device comprising a substrate, a planarization layer, a first electrode, a pixel division layer, a light-emitting pixel, and a second electrode in this order, the pixel division layer comprising a layer (A) and a layer (B), the layer (A) is a layer arranged on the surface of the first electrode in a manner so that the surface of the first electrode is partially exposed, the layer (B) is a layer arranged on at least a part of the surface of the layer (A), the layer (A) contains a cured product of a negative photosensitive composition (a), the negative photosensitive composition (a) contains: a pigment and / or a dye; a compound having two or more ethylenically unsaturated double bond groups in the molecule; and a photopolymerization initiator, the layer (B) contains a cured product of a positive photosensitive composition (b), the positive photosensitive composition (b) contains a resin and a photoacid generator, and the total content of the pigment and / or dye in the layer (B) is 5 parts by weight or less in 100 parts by weight of the layer (B).
[0173] As a method for forming a layer (A) using a negative photosensitive composition (a), a method preferably includes the following steps: a coating step of coating a negative photosensitive composition (a) to obtain a coating film; an exposure step of performing pattern exposure using active chemical rays containing near-ultraviolet rays through a negative exposure mask, thereby obtaining an exposed film having exposed portions and unexposed portions in the surface; a developing step of performing development using an alkaline developer to obtain a developed film; and a curing step of performing thermal curing by heating to obtain a cured film.
[0174] As a method for forming a layer (B) using a positive photosensitive composition (b), a method preferably includes the following steps: a coating step of coating a positive photosensitive composition (b) to obtain a coating film; an exposure step of performing pattern exposure using active chemical rays containing near-ultraviolet rays through a positive exposure mask to obtain an exposed film having exposed portions and unexposed portions in the surface; a developing step of performing development using an alkaline developer to obtain a developed film; and a curing step of performing thermal curing by heating to obtain a cured film.
[0175] As the coating device used in the coating process, a spin coater or a slit coater can be preferably used from the aspect of excellent thin film coating properties. After coating, pin gap pre-baking or contact pre-baking can be performed. The pre-baking temperature is preferably 50 to 150° C., and the pre-baking time is preferably 30 seconds to 5 minutes.
[0176] As the exposure device used in the exposure process, for example, a stepper, a mirror projection mask aligner (MPA), and a parallel light mask aligner (PLA) can be cited. As the active chemical rays containing near ultraviolet rays irradiated during exposure, the j line (wavelength 313nm), i line (wavelength 365nm), h line (wavelength 405nm) or g line (wavelength 436nm) of a mercury lamp can be cited, preferably the i line or a mixed ray containing the g line, h line and i line. As a negative exposure mask and a positive exposure mask, for example, a mask in which a light shielding portion formed of a metal such as chromium is formed in a pattern on the surface of one side of a substrate having a near ultraviolet light transmitting portion such as glass, quartz or film can be cited, and a pattern exposure is performed by allowing the active chemical rays to pass only from the opening portion, thereby obtaining an exposure film having an exposed portion and an unexposed portion in the surface. Alternatively, a halftone exposure mask having different transmittances of active chemical rays and having fully transparent portions and semi-transparent portions in its plane may be used for pattern exposure, thereby simultaneously forming a convex thick film portion and imparting a spacer function to at least a portion of the pixel dividing layer.
[0177] As the developing method in the developing process, for example, spraying, dipping, and immersion by spinning can be cited, and a method of immersing the exposure film for 10 seconds to 3 minutes can be cited. From the perspective of improving the in-plane uniformity of the opening width of the opening, the immersion by spinning method is preferred. As an alkaline developer, a 1.0-2.5 wt % tetramethylammonium hydroxide aqueous solution (hereinafter referred to as TMAH) is preferred, and as a commercially available product, a 2.38 wt % TMAH aqueous solution (manufactured by Tama Chemical Industry Co., Ltd.) can be cited. After the developing process, a washing treatment by spraying deionized water and / or a dewatering treatment by air jet can also be applied.
[0178] In the curing step, the developed film is thermally cured by heating, and water, developer, etc. are volatilized. Examples of the heating device include a hot air oven and an IR oven. The heating temperature is preferably 200 to 350° C., more preferably 220 to 280° C., under atmospheric pressure.
[0179] As a method for preparing a negative photosensitive composition (a) containing a pigment, the following method can be cited: a pigment dispersion is prepared by wet dispersion treatment, and then a compound having two or more ethylenically unsaturated double bond groups in the molecule, a photopolymerization initiator, and other components such as a solvent used as needed are mixed, and then added to the pigment dispersion, followed by mixing and stirring, and filtering using a filter as needed. In the wet dispersion treatment, a wet medium disperser such as a bead mill is preferably used from the perspective of excellent dispersion treatment speed, strong crushing force and economic advantage. From the perspective of improving luminous reliability, the cumulative 50% particle size of the pigment in the pigment dispersion and the negative photosensitive composition (a) prepared using it is preferably 20 nm or more, and more preferably 40 nm or more. From the same point of view, it is preferably 100 nm or less, and more preferably 80 nm or less. The so-called cumulative 50% particle size is the particle size equivalent to the cumulative 50% in the cumulative distribution curve of the particle size based on the light scattering intensity of the light source (semiconductor excited solid laser with a wavelength of 532 nm / 10 mW). The cumulative 50% particle size can be calculated using a dynamic light scattering particle size distribution measuring device "SZ-100" with the fine particle size as the base point (0%). In addition, from the perspective of improving luminescence reliability, the maximum particle size is preferably 400 nm or less, more preferably 300 nm or less.
[0180] On the other hand, the method for preparing the negative photosensitive composition (a) containing a dye can be prepared by the same method as the case of containing a pigment, except that the step of adding the dye to the resin or the resin solution and dissolving it is performed without requiring the aforementioned wet dispersion treatment step.
[0181] As a method for preparing the positive photosensitive composition (b), there is mentioned a method of mixing and stirring a resin, a photoacid generator, and other components such as a solvent used as needed, and filtering using a filter as needed.
[0182] Example
[0183] Hereinafter, the present invention will be described in detail with reference to Examples and Comparative Examples, but the embodiments of the present invention are not limited thereto.
[0184] First, the evaluation method in each of the Examples and Comparative Examples will be described.
[0185] <Measurement of Optimum Exposure Amount (A) of Negative Photosensitive Composition When Forming Layer (A)>
[0186] A substrate having a first electrode formed thereon and including a first electrode having a stacked pattern of silver alloy film / low-crystalline ITO was prepared by the same method as that described in Example 1 described later.
[0187] Using a spin coater, adjust the rotation speed so that the final cured film has the desired film thickness, and apply the negative photosensitive composition to the ITO surface of the substrate formed with the first electrode to obtain a coating film. Furthermore, using a hot plate, pre-bake the coating film at 110°C for 120 seconds under atmospheric pressure to obtain a pre-baked film. Use a near-infrared camera to align the negative square pattern exposure mask, and use a double-sided alignment single-sided exposure device to align the negative square pattern exposure mask (arranged with 1000 square shading portions with a vertical width of 7.0 μm and a horizontal width of 7.0 μm) at an exposure amount of 10 to 100 mJ (mJ / cm 2 The exposure amount is changed stepwise by 5 mJ each time within the range of : i line conversion value), and the pattern exposure is performed using the g, h, and i mixed rays of the ultra-high pressure mercury lamp to obtain an exposure film having an exposed portion and an unexposed portion in the surface. It should be noted that the pattern exposure is performed by bringing a negative square pattern exposure mask into contact with the surface of the pre-baked film. Next, a small developing device for lithography (AD-2000; manufactured by Takizawa Sangyo Co., Ltd.) is used to perform development by a rotary immersion method using a 2.38 wt % TMAH aqueous solution as an alkaline developer. The so-called rotary immersion method here refers to the following method: after spraying the developer on the surface of the exposure film for 10 seconds and placing the alkaline developer on the surface of the pre-baked film, it is allowed to stand together with the substrate until the specified development time is reached, thereby performing development. It should be noted that the development time is set to the time obtained by multiplying the time for the unexposed portion of the film to be dissolved and removed in the depth direction of the film by 1.5. Furthermore, after rinsing with deionized water in a spraying manner for 30 seconds, the substrate was idling at 200 rpm for 30 seconds to dry, thereby obtaining a substrate having a patterned developing film formed thereon. Next, the developing film was heated at 250°C for 1 hour in an air atmosphere using a high-temperature inert gas oven (INH-9CD-S; manufactured by Koyo Thermo Systems Co., Ltd.) to obtain a cured film containing a cured product of a negative photosensitive composition. The cured film was observed using an FPD inspection microscope (MX-61L; manufactured by Olympus Corporation), and the minimum exposure amount (mJ / cm2) when the opening was opened in a manner such that the average value of the opening width of 10 openings in the area of each exposure amount deviated from the width of the light-shielding portion of the exposure mask within the range of ±0.1 μm (i.e., 7.0 ± 0.1 μm). 2 : i-line conversion value) is used as the optimum exposure amount (A) of the negative photosensitive composition for forming the layer (A).
[0188] <Measurement of Optimum Exposure Amount (B) of Positive Photosensitive Composition When Forming Layer (B)>
[0189] On the surface of a cured film containing a cured product of a negative photosensitive composition obtained at the above-mentioned optimal exposure amount, a positive photosensitive composition is applied by using a spin coater while adjusting the rotation speed so that the cured film finally obtained has a desired film thickness, thereby obtaining a coated film. Furthermore, the coated film is pre-baked at 110°C for 120 seconds at atmospheric pressure using a heating plate to obtain a pre-baked film. A positive square pattern exposure mask is aligned using a near-infrared camera, and a double-sided alignment single-sided exposure device is used to align the positive square pattern exposure mask (with 1000 square transparent portions with a vertical width of 7.0 μm and a horizontal width of 7.0 μm) at an exposure amount of 50 to 150 mJ (mJ / cm 2 The exposure amount is changed stepwise by 5 mJ each time within the range of 1:1 (i line conversion value), and pattern exposure is performed using g, h, and i mixed rays of an ultra-high pressure mercury lamp to obtain an exposure film having an exposed portion and an unexposed portion in the surface. It should be noted that the pattern exposure is performed by bringing a positive square pattern exposure mask into contact with the surface of the pre-baked film.
[0190] Next, a small developing device for photolithography was used to develop for 80 seconds using a 2.38 wt% TMAH aqueous solution in a rotary immersion manner. The film thickness of the pre-baked film of the positive photosensitive composition and the film thickness of the developed film were respectively obtained by the difference between the film thickness of the laminated film and the film thickness of the cured film containing the cured product of the negative photosensitive composition. Furthermore, after rinsing with deionized water in a spraying manner for 30 seconds, the substrate was idling at 200 rpm for 30 seconds to dry, and a substrate with a developed film having a patterned developed film was obtained. Next, a high-temperature inert gas oven was used to heat the developed film at 250°C for 1 hour in an air atmosphere to obtain a cured film containing a cured product of the positive photosensitive composition. The cured film was observed using an FPD inspection microscope, and the minimum exposure dose (mJ / cm2) when the opening was opened so that the average value of the opening width of 10 openings in each exposure dose area relative to the width of the transmission portion of the exposure mask was within the range of ±0.1 μm (i.e., 7.0 ± 0.1 μm) was set. 2 : i-line converted value) is used as the optimum exposure amount (B) of the positive photosensitive composition for forming the layer (B).
[0191] <Measurement of Optimum Exposure Amount (A) of Positive Photosensitive Composition when Forming Layer (A) and Optimum Exposure Amount (B) of Negative Photosensitive Composition when Forming Layer (B)>
[0192] When a cured film containing a cured product of a negative photosensitive composition is formed on the surface of a cured film containing a cured product of a positive photosensitive composition, the order of the above-mentioned pattern formation is reversed, and the optimal exposure amount (A) of the positive photosensitive composition for forming layer (A) and the optimal exposure amount (B) of the negative photosensitive composition for forming layer (B) are measured respectively.
[0193] <Measurement of Optimum Exposure Amount (B) of Negative Photosensitive Composition When Forming Layer (B)>
[0194] When a cured film containing a cured product of a negative photosensitive composition is formed on the surface of a cured film containing a cured product of a negative photosensitive composition, in addition to the optimal exposure amount (A) of the negative photosensitive composition for forming layer (A) described above, the optimal exposure amount (B) of the negative photosensitive composition for forming layer (B) is measured by the same method.
[0195] In the determination of the optimum exposure amount using a negative or positive square pattern exposure mask in the above various configurations, when the shape of the opening of the cured film is not formed into a square, the short side of the opening is regarded as the opening width, and the average value of the opening width of 10 openings in the area of each exposure amount is obtained, and the optimum exposure amount (A) and the optimum exposure amount (B) are measured. However, the cured film containing an opening with an aspect ratio of 1.1 or more in the plane is excluded from the measurement object. The aspect ratio here refers to the value obtained by rounding off the second decimal place of the value obtained by dividing the length (μm) of the long side of the opening by the length (μm) of the short side. In addition, for the film thickness of the cured film, the cross-section of the film equivalent to layer (A) and layer (B) is observed using SEM, and the length is measured based on the captured image.
[0196] It should be noted that the determination of the optimal exposure amount using a negative or positive hole pattern exposure mask is carried out by the same method as the determination of the optimal exposure amount using the aforementioned negative or positive square pattern exposure mask. When the shape of the opening of the cured film is formed into a perfect circle, its diameter is regarded as the opening width, and when it is formed into an ellipse, its short axis is regarded as the opening width. The average value of the opening width of 10 openings in the area of each exposure amount is obtained, and the optimal exposure amount (A) and the optimal exposure amount (B) are measured. However, the cured film containing an opening with an aspect ratio of 1.1 or more in the plane is excluded from the measurement object. The aspect ratio here refers to the value obtained by rounding off the second decimal place of the value obtained by dividing the length (μm) of the major axis of the opening by the length (μm) of the minor axis.
[0197] (1) Evaluation of optical density (OD / μm) of cured film
[0198] For the optical density evaluation substrates formed with a cured film having a film thickness of 1.5 μm obtained in Examples 1 to 11, the total optical density (Total OD value) was measured at three locations in the surface from the film surface side using a densitometer (manufactured by X-Rite; X-Rite 361T), and the average value was calculated. The second decimal place after the value obtained by dividing the average value by 1.5 was rounded off, and the obtained value was used as the OD value (OD / μm) per 1.0 μm film thickness of the cured film. The evaluation was performed based on the criterion that the higher the OD / μm, the better the light-shielding property of the cured film. The OD value of TEMPAX without forming a cured film was separately measured, and the result was 0.00, so the OD value of the optical density evaluation substrate was regarded as the OD value of the cured film. The thickness of the cured film was determined by rounding off the average value measured at three locations within the surface using a stylus-type film thickness measuring device (Tokyo Seimitsu Co., Ltd.; SURFCOM). It should be noted that when the aforementioned optimal exposure amount could not be measured due to insufficient resolution, it was recorded as being unable to be evaluated.
[0199] (2) Evaluation of the resolution of the display unit of an organic EL display device
[0200] The organic EL display devices obtained in Examples 1 to 15, Comparative Examples 1 to 2, and Comparative Examples 4 to 14 were kept at 10 mA / cm with the light emitting surface facing upward. 2 The organic EL display device is placed in a state of emitting light by direct current driving at room temperature, and the luminescent pixel portion located in the central portion of the luminescent pixel portion is enlarged and displayed on the monitor and the length is measured. When the average value of the short diameter (the diameter in the case of a perfect circle, the short axis in the case of an ellipse) of 20 luminescent pixel portions is less than 20.0 μm, the resolution of the display portion of the organic EL display device is excellent and is recorded as qualified. On the other hand, in the case of more than 20.0 μm, the resolution of the display portion of the organic EL display device is insufficient and is recorded as unqualified. In addition, when more than one unlit pixel is observed, it is recorded as unqualified regardless of the resolution.
[0201] (3) Evaluation of the light emission reliability of organic EL display devices (high temperature continuous drive test)
[0202] The organic EL display devices obtained in Examples 1 to 12, Comparative Examples 1 to 2, and Comparative Examples 4 to 11 were placed on a hot plate maintained at 85° C. with the light emitting surface facing upward and a current of 10 mA / cm was passed through the hot plate. 2 The 20 luminescent pixel units located in the central part of the luminescent pixel unit were magnified and displayed on a monitor for observation, and the area ratio of the luminescent portion relative to the area of the luminescent pixel unit (pixel luminescent area ratio) was measured 1 hour and 200 hours after the start of driving.
[0203] The less likely the pixel shrinkage (non-luminescent portion) is to occur, and the higher the pixel luminescent area ratio can be maintained after 200 hours based on the pixel luminescent area ratio after 1 hour, the better the luminescent reliability is. An example of layer (A), luminescent portion, and non-luminescent portion when observing the luminescent pixel portion is shown in FIG. Fig.10 .
[0204] Evaluation was performed based on the following criteria, with AA and A to C being considered acceptable and D to F being considered unacceptable. It should be noted that when an opening having a desired opening width was not formed in the above-described measurement of the optimum exposure, it was difficult to perform an accurate evaluation, so this was evaluated as F.
[0205] AA: The pixel light emitting area ratio is 95% or more.
[0206] A: The pixel light emitting area ratio is 90% or more and less than 95%.
[0207] B: The pixel light emitting area ratio is 85% or more and less than 90%.
[0208] C: The pixel light emitting area ratio is 80% or more and less than 85%.
[0209] D: The pixel light emitting area ratio is 75% or more and less than 80%.
[0210] E: The pixel light emitting area ratio is less than 75%.
[0211] F: The pixel light emitting area ratio is difficult to evaluate due to insufficient resolution.
[0212] (4) Evaluation of the light emission reliability of organic EL display devices (light resistance test)
[0213] The organic EL display devices obtained in Examples 13 to 15 and Comparative Examples 12 to 14 were placed with the light emitting surface facing upward and subjected to a 10 mA / cm 2 The display unit of the organic EL display device is kept lit by direct current driving to emit light at room temperature. Simulated sunlight containing near-ultraviolet light is continuously irradiated with a xenon lamp as the light source and an illuminance of 3.0 W / cm at a wavelength of 420 nm. 2of light. The 20 light-emitting pixel portions located in the central portion of the light-emitting pixel portion were magnified and displayed on the monitor for observation, and the area ratio of the light-emitting portion relative to the area of the light-emitting pixel portion (pixel light-emitting area ratio) was measured 1 hour and 200 hours after the start of driving. The less likely the pixel shrinkage (non-light-emitting portion) is to occur, and the higher the level at which the pixel light-emitting area ratio after 200 hours can be maintained based on the pixel light-emitting area ratio after 1 hour, the better the light-emitting reliability is. Evaluation was performed based on the following criteria, with AA and A to C being considered qualified and D to F being considered unqualified. It should be noted that when an opening portion with the desired opening width cannot be formed in the aforementioned measurement of the optimal exposure amount, it is difficult to make a correct evaluation, and therefore it is evaluated as F.
[0214] AA: The pixel light emitting area ratio is 95% or more.
[0215] A: The pixel light emitting area ratio is 90% or more and less than 95%.
[0216] B: The pixel light emitting area ratio is 85% or more and less than 90%.
[0217] C: The pixel light emitting area ratio is 80% or more and less than 85%.
[0218] D: The pixel light emitting area ratio is 75% or more and less than 80%.
[0219] E: The pixel light emitting area ratio is less than 75%.
[0220] F: The pixel light emitting area ratio is difficult to evaluate due to insufficient resolution.
[0221] The following shows information on various raw materials used in Examples and Comparative Examples.
[0222] "Benzodifuranone-based black pigment A": a black pigment comprising 100 parts by weight of a benzodifuranone-based black pigment represented by formula (3) as a core and 10 parts by weight of silicon dioxide as a coating material. This is equivalent to the benzodifuranone-based black pigment 2 having a coating layer comprising silicon dioxide on the surface as described in Synthesis Example 3 of Patent Document 1 (International Publication No. 2021 / 111860). The specific surface area based on the BET method is 40 m 2 / g.
[0223] “CI Pigment Red 179”: As a commercially available product, “PALIOGEN” (registered trademark) RED L3875 (manufactured by BASF) was used.
[0224] “CI Pigment Violet 29”: As a commercially available product, “PALIOGEN” (registered trademark) REDVIOLET K5411 (manufactured by BASF) was used.
[0225] “Pigment dispersant 1”: A compound represented by formula (20). Alkali-soluble polyamine (solid content: 100% by weight). Corresponding to dispersant 5 described in Patent Document 1 (International Publication No. 2021 / 111860).
[0226] [Chemical formula 18]
[0227]
[0228] "TR4020G": Novolac type phenolic resin which is an alkali-soluble phenolic resin having no ethylenically unsaturated double bond group. Solid content: 100% by weight (manufactured by Asahi Organic Materials Co., Ltd.).
[0229] "ZCR-1569H": PGM EA solution of alkali-soluble epoxy acrylate having a biphenyl skeleton. Solid content: 70% by weight (manufactured by Nippon Kayaku Co., Ltd.). A compound having two or more ethylenically unsaturated double bond groups in the molecule.
[0230] "DPCA-20": "KAYARAD" (registered trademark) DPCA-20 (manufactured by Nippon Kayaku Co., Ltd.). A compound having six ethylenically unsaturated double bond groups in the molecule. Solid content: 100% by weight.
[0231] "DPCA-60": "KAYARAD" (registered trademark) DPCA-60 (manufactured by Nippon Kayaku Co., Ltd.). A compound having six ethylenically unsaturated double bond groups in the molecule. Solid content: 100% by weight.
[0232] "EA-0250P": "OGSOL" (registered trademark) EA-0250P (manufactured by Osaka Gas Chemicals Co., Ltd.). A compound having two ethylenically unsaturated double bond groups in the molecule. A PGMEA solution having a solid content of 50% by weight.
[0233] "BP-4EAL": "LIGHT ACRYLATE" (registered trademark) BP-4EAL (manufactured by Kyoeisha Chemical Co., Ltd.). A compound having two ethylenically unsaturated double bond groups in the molecule. Solid content: 100% by weight.
[0234] “Photopolymerization initiator 1”: A compound represented by formula (21). This is the same compound as the compound represented by structural formula (31) described in Patent Document 1 (International Publication No. 2021 / 111860).
[0235] [Chemical formula 19]
[0236]
[0237] "MEK-ST-40": a silica particle dispersion containing silica particles with a primary particle size distribution of 10 to 15 nm and an aspect ratio of 1.0 to 1.1, and an average primary particle size of 12 nm (manufactured by Nissan Chemical Industries, Ltd.). The silica particle content is 40% by weight, the solid content is 40% by weight, and the solvent is methyl ethyl ketone.
[0238] "HMOM-TPHAP": a compound represented by formula (17) (manufactured by Honshu Chemical Industry Co., Ltd.)
[0239] (Synthesis Example 1: Synthesis of Hydroxyl-Containing Diamine Compound A)
[0240] 18.3 g (0.05 mol) of 2,2-bis (3-amino-4-hydroxyphenyl) hexafluoropropane was dissolved in 100 mL of acetone and 17.4 g (0.3 mol) of propylene oxide, and the mixture was cooled to -15°C. A solution obtained by dissolving 0.11 mol (20.4 g) of 3-nitrobenzoyl chloride in 100 mL of acetone was added dropwise thereto. After the addition was completed, the mixture was reacted at -15°C for 4 hours, and then returned to room temperature. The precipitated white solid was separated by filtration and vacuum dried at 50°C. 30 g of the solid was placed in a 300 mL stainless steel autoclave, dispersed in 250 mL of methyl cellosolve, and 2 g of 5% palladium-carbon was added. Hydrogen was introduced into the mixture using a balloon, and a reduction reaction was carried out at room temperature. After about 2 hours, it was confirmed that the balloon was no longer deflated, and the reaction was completed. After the reaction was completed, the palladium compound as a catalyst was removed by filtration, and the mixture was concentrated using a rotary evaporator to obtain a hydroxyl group-containing diamine compound A represented by formula (22).
[0241] [Chemical formula 20]
[0242]
[0243] (Synthesis Example 2: Synthesis of Alkali-Soluble Polyimide Precursor A)
[0244] Under a dry nitrogen stream, 31.0 g (0.10 mol) of 3,3',4,4'-diphenylether tetracarboxylic dianhydride was dissolved in 500 g of N-methylpyrrolidone (hereinafter referred to as "NMP") as a solvent. 45.35 g (0.075 mol) of the hydroxyl-containing diamine compound A obtained in Synthesis Example 1 and 1.24 g (0.005 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane were added together with 50 g of NMP, and the mixture was reacted at 20°C for 1 hour and then at 50°C for 2 hours. 4.36 g (0.04 mol) of 4-aminophenol as a terminal blocking agent was added together with 5 g of NMP, and the mixture was reacted at 50°C for 2 hours. Then, 28.6 g (0.24 mol) of N,N-dimethylformamide dimethyl acetal 50 g was added. After the addition, the mixture was stirred at 50°C for 3 hours. After the stirring was completed, the solution was cooled to room temperature and then poured into 3L of water to obtain a white precipitate. The above operation was repeated 5 times, and the obtained white precipitate was collected in the form of a filter residue, washed with water 5 times, and dried in a vacuum dryer at 80°C for 24 hours to obtain an alkali-soluble polyimide precursor A. The alkali-soluble polyimide precursor A is a powder with a solid content of 100% by weight, a weight-average molecular weight (Mw) of 25,000, and is a resin having a structural unit represented by formula (11).
[0245] (Synthesis Example 3: Synthesis of Alkali-Soluble Polyimide B)
[0246] Under a dry nitrogen stream, 58.60 g (0.16 mol) of 2,2-bis (3-amino-4-hydroxyphenyl) hexafluoropropane and 8.73 g (0.08 mol) of 3-aminophenol as a capping agent were dissolved in 300.00 g of NMP. 62.04 g (0.20 mol) of 3,3',4,4'-diphenylether tetracarboxylic dianhydride were added thereto together with 100.00 g of NMP, stirred at 20°C for 1 hour, and then stirred at 50°C for 4 hours. Then, 15 g of xylene was added, and water and xylene were azeotroped together while stirring at 150°C for 5 hours. After the stirring was completed, the solution was put into 5 L of water and a white precipitate was collected. The precipitate was collected by filtration, washed with water 3 times, and then dried in a vacuum dryer at 80°C for 24 hours to obtain an alkali-soluble polyimide B. The alkali-soluble polyimide B is in the form of a powder having a solid content of 100% by weight, has a weight average molecular weight (Mw) of 28,000, and is a resin having a structural unit represented by formula (10).
[0247] (Synthesis Example 4: Synthesis of Quinonediazide Compound C)
[0248] Under a dry nitrogen stream, 21.22 g (0.05 mol) of TrisP-PA (manufactured by Honshu Chemical Industry Co., Ltd.) and 36.27 g (0.135 mol) of naphthoquinone diazide-5-sulfonyl chloride were dissolved in 450 g of 1,4-dioxane and the mixture was brought to room temperature. A liquid obtained by dissolving 15.18 g of triethylamine in 50.00 g of 1,4-dioxane was added dropwise thereto so that the temperature in the system was below 35°C. After the addition, the mixture was stirred at 30°C for 2 hours. The triethylamine salt was filtered and the filtrate was put into water. The mixture was then filtered and the precipitate was collected. The precipitate was dried in a vacuum dryer to obtain a quinone diazide compound C represented by formula (23).
[0249] [Chemical formula 21]
[0250]
[0251] In the formula (23), * represents a bonding site with an oxygen atom.
[0252] (Synthesis Example 5: Synthesis of Alkali-Soluble Methacrylic Resin Solution D)
[0253] Prepare a mixed solution of 65.07g of 2-hydroxyethyl methacrylate (0.50mol), 211.45g of benzyl methacrylate (1.20mol), 25.83g of methacrylic acid (0.30mol), 5.00g of 2,2'-azobis(isobutyronitrile) as a thermal polymerization initiator, and 200.00g of PGMEA. Under a dry nitrogen stream, the liquid temperature was maintained at 90°C, and a funnel was used to drop it into 261.02g of PGMEA under stirring for 1 hour. Then, the solution was heated to 120°C and maintained, and copolymerization was carried out while stirring until the weight average molecular weight (Mw) of the final copolymer obtained became 8000 to obtain a resin solution. After cooling it to 25°C, it was diluted with PGMEA in a manner that the solid content became 30% by weight to obtain an alkali-soluble methacrylic resin solution D. The alkali-soluble methacrylic resin solution D is a PGMEA solution containing a copolymer formed at a mol% ratio of 2-hydroxyethyl methacrylate / benzyl methacrylate / methacrylic acid=25 / 60 / 15.
[0254] (Synthesis Example 6: Synthesis of Alkali-soluble Acrylic Resin Solution E)
[0255] Under a dry nitrogen stream, the liquid temperature was maintained at 120°C, and a mixture of 72.10 g of 4-hydroxybutyl acrylate (0.50 mol), 92.15 g of 2-ethylhexyl acrylate (0.50 mol), 1.47 g of acrylic acid (0.02 mol), and 8.16 g of tert-butyl peroxy-2-ethylhexanoate as a polymerization initiator was added dropwise to 260.83 g of PGMEA under stirring over 1 hour using a funnel, and copolymerization was performed by stirring at 120°C until the weight average molecular weight of the final copolymer obtained reached 10,000, thereby obtaining a resin solution. After cooling it to 25°C, it was diluted with PGMEA to a solid content of 30% by weight to obtain an alkali-soluble acrylic resin solution E. The alkali-soluble acrylic resin solution E is a PGMEA solution containing a copolymer formed at a mol% ratio of 4-hydroxybutyl acrylate: 2-ethylhexyl acrylate: acrylic acid = 49:49:2.
[0256] (Synthesis Example 7: Synthesis of Fluorene Acrylate Solution F)
[0257] 400.00 g of methyl isobutyl ketone as a solvent was placed in a flask, and 350.00 g of 9,9-bis(6-glycidyloxy-2-naphthyl)fluorene, 112.10 g of acrylic acid, 1.50 g of p-hydroxyanisole as a polymerization inhibitor, and 0.30 g of tetraethylammonium bromide as a catalyst were added thereto. The liquid temperature was maintained at 120° C., and the mixture was stirred for 10 hours to react. Then, the heating was stopped and the mixture was cooled to room temperature. The reactant was washed with water by a liquid separation operation and further dried under reduced pressure to obtain fluorene acrylate (a mol% ratio of the compound represented by formula (24): the compound represented by formula (25) = 91:9). Next, PGMEA was added so that the solid content was 30% by weight, and the mixture was stirred to obtain a fluorene acrylate solution F.
[0258] [Chemical formula 22]
[0259]
[0260] [Chemical formula 23]
[0261]
[0262] (Synthesis Example 8: Synthesis of Fluorene Acrylate Solution G)
[0263] 200.00 g of PGMEA was placed in a flask, and 275.33 g (0.50 mol) of a fluorene compound represented by formula (26) (manufactured by Osaka Gas Chemicals Co., Ltd.), 72.06 g of acrylic acid (1.00 mol), 0.50 g of p-hydroxyanisole, and 0.15 g of tetraethylammonium bromide were added thereto, and the liquid temperature was maintained at 100° C. and stirred for 2 hours. Then, the liquid temperature was raised to 120° C. and stirred for 10 hours to allow the reaction to proceed.
[0264] [Chemical formula 24]
[0265]
[0266] 96.10 g (0.25 mol) of the acid dianhydride represented by formula (27) synthesized based on Example 1 of International Publication No. 2011 / 099518 was further added, and the mixture was stirred for 5 hours to carry out the reaction. 30.43 g (0.20 mol) of 1,2,3,6-tetrahydrophthalic anhydride was added, and the mixture was stirred at 90° C. for 5 hours, then the heating was stopped and the mixture was cooled to room temperature.
[0267] [Chemical formula 25]
[0268]
[0269] Next, PGMEA was added so that the solid content became 30% by weight, and the mixture was stirred to obtain a fluorene acrylate solution G containing an alkali-soluble epoxy acrylate having a structural unit represented by formula (28).
[0270] [Chemical formula 26]
[0271]
[0272] In formula (28), * represents a bonding site.
[0273] (Manufacturing Example 1: Manufacture of Pigment Dispersion Liquid 1)
[0274] 37.50 g of pigment dispersant 1 and 53.57 g of ZCR-1569H (solid content 70.00 wt%) were mixed in 783.93 g of PGMEA as a solvent, stirred for 10 minutes, and then 125.00 g of benzodifuranone black pigment A was added and stirred for 30 minutes to obtain a pre-stirred liquid. The pre-stirred liquid was sent to a bead mill filled with 0.4 mm φ zirconium oxide beads (Toray Industries, Inc. "TORAYCERAM" (registered trademark)) and subjected to a wet media dispersion treatment in a circulation manner for 30 minutes. The pre-stirred liquid was further sent to a bead mill filled with 0.05 mm φ zirconium oxide beads (Toray Industries, Inc. "TORAYCERAM" (registered trademark)) and subjected to a wet media dispersion treatment in a circulation manner until the cumulative 50% particle size in the particle size distribution of the pigment reached 99 nm, to obtain a pigment dispersion 1 having a solid content of 20.00 wt%. The weight (g) of each raw material, the cumulative 50% particle size and the maximum particle size are shown in Table 1. It should be noted that for the cumulative 50% particle size and the maximum particle size, 99.90g of PGMEA was added to each 0.10g of the pigment dispersion collected by the dispersion time and the liquid obtained by dilution was used as a measurement sample, and was set in a particle size distribution measuring device "SZ-100" ((Strain) Horiba Manufacturing Co., Ltd.), and the cumulative 50% particle size was automatically output and the end point of the wet media dispersion treatment was determined. In addition, based on the particle size distribution, the largest particle size detected was used as the maximum particle size.
[0275] [Table 1]
[0276]
[0277] (Manufacturing Example 2: Manufacture of Pigment Dispersion Liquid 2)
[0278] The dispersion time was extended in a cyclic manner until the cumulative 50% particle size in the particle size distribution of the pigment reached 60 nm. A wet medium dispersion treatment was performed in the same manner as in Production Example 1 to obtain a pigment dispersion 2 having a solid content of 20.00% by weight. The blending weight (g), cumulative 50% particle size and maximum particle size of each raw material are shown in Table 1.
[0279] (Manufacturing Example 3: Manufacture of Pigment Dispersion Liquid 3)
[0280] CI Pigment Red 179 was used instead of benzodifuranone black pigment A, and the dispersion time was extended in a cyclic manner until the cumulative 50% particle size in the particle size distribution of the pigment reached 60 nm. A wet medium dispersion treatment was performed in the same manner as in Production Example 1 to obtain a pigment dispersion 3 having a solid content of 20.00% by weight. The blending weight (g), cumulative 50% particle size and maximum particle size of each raw material are shown in Table 1.
[0281] (Manufacturing Example 4: Manufacture of Pigment Dispersion Liquid 4)
[0282] CI Pigment Violet 29 was used instead of the benzodifuranone black pigment A, and the dispersion time was extended in a cyclic manner until the cumulative 50% particle size in the particle size distribution of the pigment reached 60 nm. A wet medium dispersion treatment was performed in the same manner as in Production Example 1 to obtain a pigment dispersion 4 having a solid content of 20.00% by weight. The blending weight (g), cumulative 50% particle size and maximum particle size of each raw material are shown in Table 1.
[0283] (Manufacturing Example 5: Manufacture of Pigment Dispersion Liquid 5)
[0284] (a) Preparation of Perylene-Based Dark Purple Pigment B
[0285] 1,000.00 g of "Spectrasense (registered trademark)" Black K0087 (manufactured by BASF) was heated in an oven at 250°C under atmospheric pressure and air for 1 hour, cooled to room temperature, and then dried and aggregated by a ball mill to obtain a dark purple pigment.
[0286] 500.00 g of dark purple pigment, 2.5 kg of ground material (sodium chloride particles), and 250.00 g of dipropylene glycol were mixed and placed in a stainless steel 1-gallon kneader (manufactured by Inoue Seisakusho Co., Ltd.), and kneaded at 90° C. for 8 hours. The kneaded product was placed in 5 L of warm water, stirred for 1 hour while maintaining at 70° C. to form a slurry, and filtered and washed repeatedly to remove the ground material and dipropylene glycol. After further drying in an oven at 100° C. under atmospheric pressure / air for 6 hours, the dried agglomerate was decomposed using a ball mill to obtain a perylene-based dark purple pigment B formed by an isomer mixture of a compound represented by formula (5) and a compound represented by formula (6) as 3,4,9,10-perylenetetracarboxylic acid bisbenzimidazole.
[0287] (b) Production of Perylene Pigment Dispersant C
[0288] 50.00 g of CI Pigment Red 178 as a perylene organic pigment was dissolved in 500.00 g of 80 wt % concentrated sulfuric acid, heated, stirred at a liquid temperature of 70° C. for 6 hours, and a sulfonation reaction was performed. Then, 5 kg of ice water was added to obtain a slurry containing a precipitate, which was filtered. Then, the filter residue was washed with ethanol, washed with water, and dried at 80° C. for 24 hours under reduced pressure. A Nano Jetmizer (made by Aishin Na no Technologies CO., LTD.) was further used to perform dry pulverization treatment to obtain a perylene pigment type dispersant C represented by formula (29) as a mixture of monosulfonic acid, disulfonic acid and trisulfonic acid.
[0289] [Chemical formula 27]
[0290]
[0291] (c) Production of Pigment Dispersion Liquid 5
[0292] A pigment dispersion 5 having a solid content of 20.00 wt % was obtained by performing a wet medium dispersion treatment in the same manner as in Production Example 1 except that the perylene-based dark purple pigment B, perylene-based pigment type dispersant C and fluorene acrylate solution G as a dispersing resin were used and the blending amounts of the raw materials were set to those shown in Table 1. The cumulative 50% particle size and the maximum particle size are shown in Table 1.
[0293] (Manufacturing Example 6: Manufacture of Pigment Dispersion Liquid 6)
[0294] A wet media dispersion treatment was attempted in the same manner as in Production Example 1 except that perylene-based dark purple pigment B was used instead of benzodifuranone-based black pigment A. However, a significant increase in viscosity occurred before the cumulative 50% particle size in the particle size distribution of the pigment reached 99 nm, and the internal pressure of the pump increased, making it difficult to feed the liquid into the bead mill, so that pigment dispersion 6 could not be obtained. Table 1 shows the blending amount of each raw material.
[0295] (Manufacturing Example 7: Manufacture of Pigment Dispersion Liquid 7)
[0296] 142.22 g of "DISPERBYK (registered trademark)" 2001 (manufactured by BYK Chemie Japan (KK); solution with a solid content of 45% by weight) as an acrylic dispersant was added to 721.78 g of a mixed solvent (weight ratio of PGME:PGMEA=20:80) and stirred for 10 minutes. Next, 94.00 g of CI Pigment Green 59 (manufactured by DIC (KK)) and 42.00 g of CI Pigment Yellow 150 (manufactured by LANXESS) were mixed and stirred for 30 minutes to obtain a pre-stirred liquid. The pre-stirred liquid was sent to a bead mill filled with 0.4 mmφ zirconium oxide beads ("TORAYCERAM" (registered trademark) manufactured by Toray Industries, Ltd.) and subjected to a wet media dispersion treatment for 5 hours in a circulation system to obtain a pigment dispersion 7 with a solid content of 20.00% by weight.
[0297] (Preparation Example 1: Preparation of positive photosensitive composition 1)
[0298] Under a yellow light, 7.50 g of an alkali-soluble polyimide precursor A, 2.25 g of a quinonediazide compound C, and 5.25 g of HMOM-TP HAP as a thermal crosslinking agent were added to 85.00 g of a mixed solvent (PGME: ethyl lactate: γ-butyrolactone = 50:40:10 weight ratio) and stirred for 30 minutes to dissolve the mixture, thereby obtaining a positive photosensitive composition 1 having a solid content of 15.00 weight %. The blending weights of the raw materials are shown in Table 2.
[0299] [Table 2]
[0300]
[0301] (Preparation Examples 2-3: Preparation of positive photosensitive compositions 2-3)
[0302] Positive photosensitive compositions 2 and 3 were prepared in the same manner as in Preparation Example 1 except that alkali-soluble polyimide B or TR4020G (manufactured by Asahi Organic Materials Co., Ltd.) as an alkali-soluble phenol resin was used instead of alkali-soluble polyimide precursor A. Table 2 shows the blending weight of each raw material.
[0303] (Preparation Example 4: Preparation of Negative Photosensitive Composition 1)
[0304] Under a yellow light, 0.60 g of photopolymerization initiator 1 was added to a mixed solvent of 8.50 g of MBA and 43.03 g of PGMEA, and the mixture was stirred for 3 minutes to dissolve. 3.15 g of ZCR-1569H and 10.00 g of alkali-soluble methacrylic resin solution D were added thereto. Next, 0.75 g of DPCA-60 (manufactured by Nippon Kayaku Co., Ltd.) and 3.90 g of EA-0250P (a PGMEA solution having a solid content of 50% by weight. Manufactured by Osaka Gas Chemicals Co., Ltd.) were added. 0.60 g of TEPIC-L (manufactured by Nissan Chemical Industries, Ltd.) was further added as a thermal crosslinking agent, and the mixture was stirred for 10 minutes to obtain a prepared solution. The prepared solution was mixed with 29.48 g of pigment dispersion 1 and stirred for 30 minutes to obtain a negative photosensitive composition 1 having a solid content of 15.00% by weight. Table 3 shows the blending amount (g) of each raw material.
[0305] [Table 3]
[0306]
[0307] (Preparation Example 5: Preparation of Negative Photosensitive Composition 2)
[0308] Under a yellow light, add 0.60 g of NCI-831E to a mixed solvent of 4.25 g of MBA and 42.21 g of PGMEA, and stir for 3 minutes to dissolve it. Add 4.29 g of ZCR-1569H and 2.00 g of alkali-soluble acrylic resin solution E thereto. Next, add 0.75 g of DPCA-20, 2.40 g of EA-0250P, and 0.75 g of "LIGHT AC RYLATE" (registered trademark) BP-4EAL (manufactured by Kyoeisha Chemical Co., Ltd.). Further, add 3.00 g of a PGMEA solution having a solid content of 5% by weight of Emulgen A-60, stir for 10 minutes, and obtain a prepared solution. The prepared solution is mixed with 39.75 g of pigment dispersion 1, stirred for 30 minutes, and a negative photosensitive composition 2 having a solid content of 15.00% by weight is obtained. The amount (g) of each raw material is shown in Table 3. The 5 wt% PGMEA solution of Emulgen A-60 was prepared by dissolving 5 parts by weight of "Emulgen" (registered trademark) A-60 (manufactured by Kao Corporation) as a nonionic surfactant in 95 parts by weight of PGMEA.
[0309] (Preparation Example 6: Preparation of Negative Photosensitive Composition 3)
[0310] Under a yellow light, 0.60 g of "Irgacure" (registered trademark) OXE03 ("OXE03" in Table 4) as a photopolymerization initiator was added to a mixed solvent of 8.50 g of MBA and 39.94 g of PGMEA, and the mixture was stirred for 3 minutes to dissolve. 11.00 g of alkali-soluble methacrylic resin solution D and 1.60 g of TR4020G as an alkali-soluble phenolic resin were added thereto. Next, 0.75 g of DPCA-60, 7.50 g of fluorene acrylate solution F, and 0.60 g of TEPIC-L were added. 0.03 g of a 5 wt% PGMEA solution of BY K-333 (manufactured by BYK Chemie Japan (KK)) as a silicone leveling agent was further added, and the mixture was stirred for 10 minutes to obtain a prepared solution. This prepared liquid was mixed with 29.48 g of the pigment dispersion 2, and stirred for 30 minutes to obtain a negative photosensitive composition 3 having a solid content of 15.00% by weight. Table 4 shows the blending amount (g) of each raw material.
[0311] [Table 4]
[0312]
[0313] (Preparation Examples 7 to 9: Preparation of Negative Photosensitive Compositions 4 to 6)
[0314] Negative photosensitive compositions 4 to 6 having a solid content of 15.00 wt % were obtained by the same procedure as in Preparation Example 6 except that MEK-ST-40 or pigment dispersions 3 to 4 were used and the blending amounts (g) of the respective raw materials shown in Table 4 were used.
[0315] (Preparation Example 10: Preparation of Negative Photosensitive Composition 7)
[0316] Under a yellow light, 1.20 g of CI Solvent Blue 97 as an anthraquinone dye, 0.60 g of CI Solvent Yellow 93 as a methine dye, and 1.20 g of CI Acid Red 52 as a xanthene dye were added to 67.55 g of a mixed solvent (PGME:PGMEA:γ-butyrolactone=30:60:10 weight ratio) and stirred for 2 hours. Next, 0.60 g of "Irgacure" (registered trademark) OXE03 ("OXE03" in Table 5) was added and stirred for 3 minutes to dissolve. 1.71 g of ZCR-1569H, 16.65 g of alkali-soluble methacrylic resin solution D, and 1.60 g of TR4020G were added thereto. Next, 0.75 g of DPCA-60, 7.50 g of fluorene acrylate solution F, and 0.60 g of TEPIC-L were added. Furthermore, 0.03 g of a 5 wt % PGMEA solution of BYK-333 was added as a silicone leveling agent, and the mixture was stirred for 30 minutes to obtain a negative photosensitive composition 7 having a solid content of 15.00 wt %. Table 5 shows the blending amount (g) of each raw material.
[0317] [Table 5]
[0318] @Table 5@
[0319]
[0320] (Preparation Example 11: Preparation of Negative Photosensitive Composition 8)
[0321] Except having used the alkali-soluble polyimide B instead of the alkali-soluble methacrylic resin solution D, the negative photosensitive composition 8 having a solid content of 15.00 wt % was obtained by the same method as in Preparation Example 4 with the blending amounts (g) of the respective raw materials shown in Table 6.
[0322] [Table 6]
[0323]
[0324] (Preparation Example 12: Preparation of Negative Photosensitive Composition 9)
[0325] A negative photosensitive composition 9 having a solid content of 15.00 wt % was obtained by the same method as in Preparation Example 4 with the blending amounts (g) of the respective raw materials shown in Table 6 except that the pigment dispersion 1 and EA-0250P were not used.
[0326] (Preparation Example 13: Preparation of Negative Photosensitive Composition 10)
[0327] A negative photosensitive composition 10 having a solid content of 15.00 wt % was obtained by the same method as in Preparation Example 4 with the blending amounts (g) of the respective raw materials shown in Table 6, except that the pigment dispersion 5 was used instead of the pigment dispersion 1 and the fluorene acrylate solution F was used instead of EA-0250P.
[0328] (Preparation Example 14: Preparation of Negative Photosensitive Green Composition for Color Filter)
[0329] Under a yellow light, 0.60 g of "Irgacure" (registered trademark) OXE03 was added to 34.26 g of a mixed solvent (PGME:PGMEA = 20:80 weight ratio) and stirred for 5 minutes to dissolve it. Further, 31.71 g of an alkali-soluble methacrylic resin solution D and 4.00 g of DPCA-60 were added and stirred for 10 minutes to obtain a mixed solution. The mixed solution was mixed with 29.43 g of a pigment dispersion 7 and stirred for 30 minutes to obtain a negative photosensitive green composition for a color filter having a solid content of 20.00% by weight.
[0330] (Example 1)
[0331] The negative photosensitive composition 1 was applied on the surface of "TEMPAX (manufactured by AGC TECHNO GLASS Co., Ltd.) as a transparent glass substrate by means of a spin coater while adjusting the rotation speed so that the thickness of the cured film finally obtained would be 1.5 μm, thereby obtaining a coated film. The coated film was pre-baked at 110° C. for 120 seconds under atmospheric pressure using a hot plate (SCW-636; manufactured by Dainippon Screen Mfg. Co., Ltd.) to obtain a pre-baked film. A double-sided alignment single-sided exposure device was used to irradiate the entire surface of the pre-baked film with mixed g, h, and i rays of an ultra-high pressure mercury lamp at the optimal exposure amount (A) determined by the above method to obtain an exposed film. Subsequently, development, rinsing, and drying were performed by the same method as when the optimal exposure amount (A) was measured to obtain a solid developed film. A high-temperature inert gas oven (INH-9CD-S; Koyo Thermo Systems The developed film was heated at 250°C for 1 hour in an air atmosphere to obtain a substrate for optical density evaluation of a solid cured film with a film thickness of 1.5 μm, and the optical density (OD / μm) of the cured product of the negative photosensitive composition 1 per 1.0 μm film thickness was evaluated by the aforementioned method.
[0332] Next, a substrate for optical density evaluation having a solid cured film with a film thickness of 1.5 μm was obtained by the same method except that the positive photosensitive composition 1 was used instead of the negative photosensitive composition 1, and no exposure was performed, and the development time was set to the same as that in the measurement of the above-mentioned optimal exposure amount (B). The optical density (OD / μm) per 1.0 μm film thickness of the cured product of the positive photosensitive composition 1 was evaluated by the above-mentioned method. The evaluation results are shown in Table 7. Furthermore, for a substrate obtained by preparing the same cured film on a silicon wafer instead of a transparent glass substrate, an infrared absorption spectrum was analyzed to confirm that the cured product of the positive photosensitive composition 1 had an imide bond and a benzoxazole skeleton.
[0333] Furthermore, an organic EL display device including a pixel division layer was produced by the following method. Fig.11 2 shows a process for producing an organic EL display device including a process for forming a pixel division layer.
[0334] Using a spin coater, the rotation speed was adjusted so that the thickness of the final flattened layer would be 1.0 μm, and the positive photosensitive composition 1 was applied to the surface of a 100 mm long / 100 mm wide alkali-free glass substrate 55 to obtain a coating film. Furthermore, a hot plate was used to pre-bake the coating film at 110°C for 120 seconds under atmospheric pressure to obtain a pre-baked film. A double-sided aligned single-sided exposure device was used to expose a positive square pattern exposure mask (with a square light-shielding portion in the center with a vertical width of 30 mm and a horizontal width of 30 mm) at a rate of 100 mJ / cm 2 The pre-baked film was pattern-exposed at an exposure amount of 1000 nm to obtain an exposed film. The exposed film was developed for 60 seconds using a 2.38 wt % TMAH aqueous solution, rinsed for 30 seconds using deionized water, and then dried by blowing air to obtain a patterned developed film. The developed film was heated at 250° C. for 1 hour in an air atmosphere using a high-temperature inert gas oven to obtain a square planarization layer 56 with a vertical width of 30 mm and a horizontal width of 30 mm.
[0335] Next, a silver alloy (an alloy formed by 99.00 wt% of silver and 1.00 wt% of copper) is formed on the entire surface by sputtering. A patterned cured film of the positive photosensitive composition 3 is used as an etching resist film, immersed in a silver alloy etching solution SE A-1 at a liquid temperature of 30°C, and etched to obtain a patterned silver alloy film with a film thickness of 50nm. Further, an ITO film is formed on the entire surface by sputtering. A positive photosensitive composition 3 is used as a resist film, immersed in a 5 wt% oxalic acid aqueous solution at a liquid temperature of 50°C for 5 minutes, rinsed with deionized water spray for 2 minutes, and then dried by blowing to obtain an ITO film of the same pattern with a film thickness of 10nm. Through the above steps, a substrate having a first electrode 57 formed by a stacked pattern of a silver alloy film and an ITO film is obtained.
[0336] Using a spin coater, the rotation speed is adjusted in such a way that the film thickness of the final layer (A) becomes 1.5 μm, and the negative photosensitive composition 1 is applied to the surface of the substrate formed with the first electrode to obtain a coating film. Further, using a hot plate, the coating film is pre-baked at 110°C for 120 seconds under atmospheric pressure to obtain a pre-baked film. Using a double-sided alignment single-sided exposure device, a negative square pattern exposure mask (arranged with 1000 square shading portions with a longitudinal width of 7.0 μm and a lateral width of 7.0 μm) is used to expose the pre-baked film in a pattern with the optimal exposure (A) obtained by the above method to obtain an exposure film. It should be noted that the pattern exposure is carried out by contacting the negative square pattern exposure mask with the surface of the pre-baked film. Then, development, rinsing and drying are carried out by the same method as the determination of the optimal exposure (A) to obtain a patterned developed film. The developed film was heated at 250° C. for 1 hour in an air atmosphere using a high-temperature inert gas oven to obtain a layer (A) having a film thickness of 1.5 μm containing a cured product of the negative photosensitive composition 1 .
[0337] Using a spin coater, the rotation speed is adjusted in such a way that the film thickness of the final layer (B) becomes 0.3 μm, and the positive photosensitive composition 1 is applied to the surface of the layer (B) to obtain a coating film. Further, the coating film is pre-baked at 110° C. for 120 seconds at atmospheric pressure using a hot plate to obtain a pre-baked film. The positive square pattern exposure mask is aligned using a near-infrared camera, and the positive square pattern exposure mask (arranged with 1000 square transmission parts with a longitudinal width of 7.0 μm and a lateral width of 7.0 μm) is used. The pre-baked film is pattern-exposed using a double-sided alignment single-sided exposure device with the optimal exposure amount (B) obtained by the above method to obtain an exposure film. It should be noted that the pattern exposure is carried out by contacting the positive square pattern exposure mask with the surface of the pre-baked film. Next, development, rinsing and drying are carried out by the same method as the determination of the optimal exposure amount (B) to obtain a patterned developed film. The developed film was heated at 250° C. for 1 hour in an air atmosphere using a high-temperature inert gas oven to obtain a layer (B) having a film thickness of 0.3 μm containing a cured product of the positive photosensitive composition 1 .
[0338] The above method obtains a substrate having a pixel segmentation layer, wherein the pixel segmentation layer 58 has 1000 openings with an opening width of 7.0 μm in an area with a longitudinal width of 30 mm and a lateral width of 30 mm in the central part of the substrate having the first electrode, and the layer (B) is arranged on the surface of the layer (A). In the pixel segmentation layer 58, at the portion where the layer (B) is arranged on the surface of the layer (A), the maximum film thickness of the layer (A) is 1.5 μm, and the maximum film thickness of the layer (B) is 0.3 μm. The area ratio of the surface of the layer (B) covering the layer (A) is 100% of the total surface area of the layer (A) (100%). Figure 3 ). It should be noted that, regarding the non-formed portion of the second electrode 60 described later, the average value obtained by measuring the film thickness after forming layer (A) and the film thickness after further forming layer (B) at three locations within the surface using a stylus-type film thickness measuring device (Tokyo Seimitsu Co., Ltd.; SURFCOM) is rounded to the second decimal place and the obtained value is used as the film thickness of layer (A) and the total value of the film thickness of layer (A) and the film thickness of layer (B). The value obtained by subtracting the film thickness of layer (A) from the total value of the film thickness of layer (A) and the film thickness of layer (B) is used as the film thickness of layer (B). Separately, the value obtained by rounding off the second decimal place of the maximum value of the film thicknesses measured at the three locations within the surface is used as the maximum value of the film thickness of layer (A). The value obtained by subtracting the minimum value of the film thickness of layer (A) from the maximum value of the total value of the film thickness of layer (A) and the film thickness of layer (B) is rounded off to the second decimal place and is taken as the maximum value of layer (B).
[0339] Next, in order to form an organic EL layer 59 including a light-emitting layer in the opening of the pixel division layer 58 by vacuum deposition, a vacuum of 1×10 -3 Under the vapor deposition conditions of less than 100 Pa, the substrate with the pixel division layer formed thereon is rotated relative to the vapor deposition source. First, the compound (HT-1) represented by formula (30) is formed into a film with a thickness of 10 nm as a hole injection layer, and the compound (HT-2) represented by formula (31) is formed into a film with a thickness of 50 nm as a hole transport layer. Next, the compound (GH-1) represented by formula (32) as a host material and the compound (GD-1) represented by formula (33) as a dopant material are vapor deposited on the light-emitting layer with a film thickness of 40 nm. Next, the compound (ET-1) represented by formula (34) as an electron transport material and the compound (LiQ) represented by formula (35) are stacked in a volume ratio of 1:1 with a film thickness of 40 nm.
[0340] [Chemical formula 28]
[0341]
[0342] [Chemical formula 29]
[0343]
[0344] [Chemical formula 30]
[0345]
[0346] [Chemical formula 31]
[0347]
[0348] [Chemical formula 32]
[0349]
[0350] [Chemical formula 33]
[0351]
[0352] Next, after evaporating a 2nm compound (LiQ), an alloy of silver and magnesium (volume ratio of 10:1) was evaporated in such a way that the film thickness became 150nm to form a second electrode 60. Next, an epoxy resin-based adhesive was used to bond a cap-shaped glass plate in a low humidity / nitrogen atmosphere, thereby sealing to obtain an organic EL display device in which green light-emitting pixels were arranged. It should be noted that the layer constituting the organic EL layer 59 is very thin compared to the aforementioned pixel division layer, so a quartz oscillation film thickness monitor suitable for thin films less than 100nm was used to measure each, and the value obtained by rounding off the second decimal place of the average value of the three points in the plane was used as the film thickness.
[0353] The light emission reliability (high temperature continuous driving test) of the organic EL display device produced by the above steps was evaluated by the above method. The evaluation results are shown in Table 7-1 and Table 7-2.
[0354] [Table 7-1]
[0355]
[0356] [Table 7-2]
[0357] [Table 7-2]
[0358]
[0359] (Example 2)
[0360] The optical density (OD / μm) of the cured film and the light emission reliability (high-temperature continuous driving test) of the organic EL display device were evaluated by the same method as in Example 1, except that the negative photosensitive composition 3 was used instead of the negative photosensitive composition 1. The evaluation results are shown in Tables 7-1 and 7-2.
[0361] (Examples 3-4)
[0362] The optical density (OD / μm) of the cured film and the light emission reliability (high temperature continuous driving test) of the organic EL display device were evaluated by the same method as in Example 1, except that the negative photosensitive composition 3 was used instead of the negative photosensitive composition 1 and the positive photosensitive compositions 2 to 3 were used instead of the positive photosensitive composition 1. The evaluation results are shown in Tables 7-1 and 7-2.
[0363] (Examples 5 to 8)
[0364] The optical density (OD / μm) of the cured film and the light emission reliability (high-temperature continuous driving test) of the organic EL display device were evaluated by the same methods as in Example 1, except that negative photosensitive compositions 4 to 7 were used instead of negative photosensitive composition 1. The evaluation results are shown in Tables 7-1, 7-2, 8-1, and 8-2.
[0365] [Table 8-1]
[0366]
[0367] [Table 8-2]
[0368]
[0369] (Example 9)
[0370] Negative photosensitive composition 4 was used instead of negative photosensitive composition 1, and the surface of layer (A) having a thickness of 1.5 μm was covered by layer (B) having a thickness of 1.5 μm, and the area ratio thereof became 20% of the total surface area of layer (A) of 100%, and the photosensitive spacer function was given to the pixel dividing layer ( Figure 4 ), in the formation of layer (B), a positive square pattern exposure mask (arranged with 500 square transmission portions with a vertical width of 20.0 μm and a horizontal width of 20.0 μm) was used instead of a positive square pattern exposure mask (arranged with 1000 square transmission portions with a vertical width of 7.0 μm and a horizontal width of 7.0 μm). Otherwise, an organic EL display device was prepared by the same method as in Example 5, and the luminescence reliability (high-temperature continuous drive test) was evaluated. The evaluation results are shown in Tables 8-1 and 8-2. It should be noted that in the portion where layer (B) is arranged on the surface of layer (A), the maximum film thickness of layer (A) is 1.5 μm, and the maximum film thickness of layer (B) is 1.5 μm.
[0371] (Example 10)
[0372] An organic EL display device was produced in the same manner as in Example 9, except that negative photosensitive composition 5 was used instead of negative photosensitive composition 4, and the light emission reliability (high-temperature continuous drive test) was evaluated. The evaluation results are shown in Tables 8-1 and 8-2.
[0373] (Example 11)
[0374] The optical density (OD / μm) of the cured film and the light emission reliability (high-temperature continuous driving test) of the organic EL display device were evaluated by the same method as in Example 1, except that the negative photosensitive composition 10 was used instead of the negative photosensitive composition 1. The evaluation results are shown in Tables 8-1 and 8-2.
[0375] (Comparative Example 1)
[0376] Except that the layer (B) was not formed, an organic EL display device was produced in the same manner as in Example 1, and the light emission reliability (high-temperature continuous drive test) was evaluated. The evaluation results are shown in Tables 9-1 and 9-2.
[0377] [Table 9-1]
[0378]
[0379] [Table 9-2]
[0380] [Table 9-2]
[0381]
[0382] (Comparative Example 2)
[0383] An organic EL display device was prepared by the same method as in Example 1, except that a positive photosensitive composition 1 was used to form layer (A) instead of a negative photosensitive composition 1, and a negative photosensitive composition 1 was used to form layer (B) instead of a positive photosensitive composition 1. The evaluation results are shown in Tables 9-1 and 9-2. The pixel division layer of the organic EL display device prepared in Comparative Example 2 is a pixel division layer in which a layer (B) containing a cured product of a negative photosensitive composition 1 (which contains a pigment, a compound having two or more ethylenically unsaturated double bond groups in the molecule, and a photopolymerization initiator) is arranged on the surface of a layer (A) containing a cured product of a positive photosensitive composition 1 containing a resin and a photoacid generator. It should be noted that the maximum film thickness of layer (A) is 0.3 μm, and the maximum film thickness of layer (B) is 1.5 μm.
[0384] (Comparative Example 3)
[0385] The negative photosensitive composition 2 was used instead of the negative photosensitive composition 1 to form the layer (A) in the same manner as in Example 1. However, due to insufficient resolution, an opening having an opening width of 7.0±0.1 μm could not be formed in the measurement of the optimum exposure amount (A). Therefore, the organic EL display device could not be produced.
[0386] (Comparative Example 4)
[0387] An organic EL display device was prepared in the same manner as in Example 1 except that the negative photosensitive composition 1 was used to form the layer (B) instead of the positive photosensitive composition 1, and the light emission reliability (high temperature continuous driving test) was evaluated. The evaluation results are shown in Tables 9-1 and 9-2.
[0388] (Comparative Example 5)
[0389] An organic EL display device was prepared by the same method as in Example 1, except that the negative photosensitive composition 8 was used to form the layer (A) instead of the negative photosensitive composition 1, and the layer (B) was not formed, and the light emission reliability (high temperature continuous driving test) was evaluated. The evaluation results are shown in Tables 9-1 and 9-2.
[0390] (Comparative Example 6)
[0391] An organic EL display device was prepared in the same manner as in Example 1 except that the negative photosensitive composition 9 was used to form the layer (B) instead of the positive photosensitive composition 1, and the light emission reliability (high temperature continuous driving test) was evaluated. The evaluation results are shown in Tables 10-1 and 10-2.
[0392] [Table 10-1]
[0393]
[0394] [Table 10-2]
[0395] [Table 10-2]
[0396]
[0397] (Comparative Example 7)
[0398] An organic EL display device was prepared by the same method as in Example 1, except that the positive photosensitive composition 3 was used to form the layer (A) instead of the negative photosensitive composition 1, and the positive photosensitive composition 3 was used instead of the positive photosensitive composition 1, and the light emission reliability (high temperature continuous driving test) was evaluated. The evaluation results are shown in Tables 10-1 and 10-2.
[0399] (Comparative Example 8)
[0400] When measuring the optimum exposure amount (A) of the negative photosensitive composition 1 for forming the layer (A), an additional exposure amount (A) of 1000 mJ (mJ / cm 2 The second exposure step is to perform full-surface exposure with mixed g, h, and i rays from an ultra-high pressure mercury lamp from the developed film side of the substrate with the developed film formed thereon with an exposure dose of 1000 mJ (mJ / cm2). When a substrate with a pixel division layer is formed, a second exposure step is performed with a exposure dose of 1000 mJ (mJ / cm2) by the same method. 2 The second exposure step of full-surface exposure with an exposure amount of 0.1: i-line conversion value) was performed, and layer (B) was not formed. The organic EL display device was prepared by the same method as in Example 1, and the light emission reliability (high-temperature continuous drive test) was evaluated. The evaluation results are shown in Tables 10-1 and 10-2.
[0401] (Comparative Example 9)
[0402] The optimal exposure amount (A) of the negative photosensitive composition 1 for forming the layer (A) and the substrate with the pixel division layer formed thereon were measured in such a manner that an opening with an opening width of 50.0±0.1 μm was obtained, and the layer (B) was not formed. Except that an organic EL display device was prepared by the same method as in Example 1, and the light emission reliability (high temperature continuous drive test) was evaluated. The evaluation results are shown in Tables 10-1 and 10-2.
[0403] (Comparative Example 10)
[0404] The optimal exposure amount (A) of the negative photosensitive composition 1 for forming the layer (A) and the substrate formed with the pixel division layer were measured in such a manner that an opening with an opening width of 30.0±0.1 μm was obtained, and the layer (B) was not formed. Except that an organic EL display device was prepared by the same method as in Example 1, and the light emission reliability (high temperature continuous drive test) was evaluated. The evaluation results are shown in Tables 10-1 and 10-2.
[0405] (Example 12)
[0406] The negative photosensitive composition 4 was used instead of the negative photosensitive composition 1, and the negative square pattern exposure mask (arranged with 1000 square light shielding portions with a vertical width of 7.0 μm and a horizontal width of 7.0 μm) was used instead of the negative square pattern exposure mask (arranged with 1000 square light shielding portions with a vertical width of 7.0 μm and a horizontal width of 7.0 μm) was used to measure the optimal exposure amount (A) of the negative photosensitive composition 4 for forming the layer (A) and to prepare a substrate with a pixel division layer so as to obtain an opening portion with an opening width of 17.0±0.1 μm. The positive hole pattern exposure mask ( The positive square pattern exposure mask (arranged with 500 perfectly circular transmission parts with a diameter of 30.0 μm) was used instead of the positive square pattern exposure mask (arranged with 1000 square transmission parts with a vertical width of 7.0 μm and a horizontal width of 7.0 μm), and the optimal exposure amount (B) of the positive photosensitive composition 1 for forming layer (B) was measured in such a way as to obtain an opening part with an opening width of 30.0±0.1 μm, and a substrate with a pixel division layer was prepared. Otherwise, an organic EL display device was prepared by the same method as in Example 1, and the luminescence reliability (high-temperature continuous drive test) was evaluated. It should be noted that the area ratio of the surface of the layer (B) covering the layer (A) is 92% of the total surface area of the layer (A) of 100%. The evaluation results (high-temperature continuous drive test) are shown in Tables 11-1 and 11-2.
[0407] [Table 11-1]
[0408]
[0409] [Table 11-2]
[0410]
[0411] (Comparative Example 11)
[0412] Except that the layer (B) was not formed, an organic EL display device was produced in the same manner as in Example 12, and the light emission reliability (high-temperature continuous driving test) was evaluated. The evaluation results are shown in Tables 11-1 and 11-2.
[0413] (Example 13)
[0414] An organic EL display device was produced in the same manner as in Example 12 except that the layer (B) was formed to have a film thickness of 0.5 μm, and the light emission reliability (light resistance test) was evaluated. The evaluation results are shown in Tables 12-1 and 12-2.
[0415] [Table 12-1]
[0416]
[0417] [Table 12-2]
[0418] [Table 12-2]
[0419]
[0420] (Comparative Example 12)
[0421] An organic EL display device was prepared in the same manner as in Example 12 except that the layer (B) was not formed so as to have a film thickness of 0.5 μm, and the light emission reliability (light resistance test) was evaluated. The evaluation results are shown in Tables 12-1 and 12-2.
[0422] (Example 14)
[0423] The layer (B) was formed to have a film thickness of 0.5 μm. An organic EL display device was produced by the same method as in Example 12. Furthermore, a color filter substrate produced by the following method was attached to the light extraction side using an epoxy adhesive to obtain an organic EL display device having a color filter substrate, and the light emission reliability (light resistance test) was evaluated. The evaluation results are shown in Tables 12-1 and 12-2.
[0424] <Production of Color Filter Substrate>
[0425] On the surface of TEMPAX as a transparent glass substrate, a negative photosensitive green composition for color filter was applied by a spin coater with the rotation speed adjusted so that the thickness of the final cured film was 1.0 μm to obtain a coating film. The coating film was pre-baked at 110°C for 120 seconds under atmospheric pressure using a hot plate to obtain a pre-baked film. A double-sided alignment single-sided exposure device was used to expose the film using a mixed g, h, and i radiation from an ultra-high pressure mercury lamp at a rate of 100 mJ / cm 2 The prebaked film was fully exposed to an exposure amount of , thereby obtaining an exposure film. The substrate having the exposure film formed thereon was heated at 230° C. for 30 minutes in an air atmosphere using a high-temperature inert gas oven to obtain a green color filter substrate.
[0426] (Comparative Example 13)
[0427] Except that the layer (B) was not formed, an organic EL display device including a color filter substrate was produced in the same manner as in Example 14, and the light emission reliability (light resistance test) was evaluated. The evaluation results are shown in Tables 12-1 and 12-2.
[0428] (Example 15)
[0429] The light emission reliability (light resistance test) of an organic EL display device including a color filter substrate produced in the same manner as in Example 14 was evaluated except that negative photosensitive composition 10 was used instead of negative photosensitive composition 4. The evaluation results are shown in Tables 12-1 and 12-2.
[0430] (Comparative Example 14)
[0431] Except that the layer (B) was not formed, an organic EL display device including a color filter substrate was produced in the same manner as in Example 15, and the light emission reliability (light resistance test) was evaluated. The evaluation results are shown in Tables 12-1 and 12-2.
[0432] From the above results, it can be seen that compared with the organic EL display devices produced in Comparative Examples 1 to 2 and 4 to 14, the organic EL display devices produced in Examples 1 to 15 have high light-shielding properties, and despite having a pixel segmentation layer with an opening portion with a narrow opening width, excellent luminescence reliability is still achieved.
[0433] Therefore, it can be seen that the organic EL display device of the present invention is useful.
[0434] Industrial Applicability
[0435] The organic EL display device of the present invention can be preferably used in applications requiring high resolution and light emission reliability of the display portion, for example, electronic devices such as small watch-type wearable devices used outdoors and foldable smartphones.
[0436] DESCRIPTION OF SYMBOLS 1: TFT
[0437] 2: Wiring
[0438] 3: TFT insulation layer 4: planarization layer
[0439] 5: First electrode
[0440] 6: Substrate 7: Contact hole 8: Layer (A)
[0441] 9: Layer (B)
[0442] 10: Pixel segmentation layer 11: Luminous pixel
[0443] 12: Second electrode 13: Substrate
[0444] 14: Black Matrix
[0445] 15: Green filter 16: Red filter 17: Blue filter 18: Substrate
[0446] 19: planarization layer 20: first electrode 21: layer (A)
[0447] 22: Layer (B)
[0448] 23: Substrate
[0449] 24: planarization layer 25: first electrode 26: layer (A)
[0450] 27: Layer (B)
[0451] 28: Substrate
[0452] 29: Flattening layer
[0453] 30: First electrode
[0454] 31: Layer (A)
[0455] 32: Layer (B)
[0456] 33: Substrate
[0457] 34: Flattening layer
[0458] 35: First electrode
[0459] 36: Layer (A)
[0460] 37: Layer (B)
[0461] 38: Substrate
[0462] 39: Flattening layer
[0463] 40: First electrode
[0464] 41: Layer (A)
[0465] 42: Layer (B)
[0466] 43: TFT
[0467] 44: Layer (A)
[0468] 45: Opening of the layer (A) where blue light-emitting pixels are arranged
[0469] 46: Opening of layer (A) where red light-emitting pixels are arranged
[0470] 47: Opening of layer (A) where green light-emitting pixels are arranged
[0471] 48: Layer (A)
[0472] 49: Opening of layer (A) where blue light-emitting pixels are arranged
[0473] 50: Opening of the layer (A) where red light-emitting pixels are arranged
[0474] 51: Opening of layer (A) where green light-emitting pixels are arranged
[0475] 52: Layer (A)
[0476] 53: Luminous part
[0477] 54: Non-luminous part
[0478] 55: Alkali-free glass substrate
[0479] 56: Flattening layer
[0480] 57: First electrode
[0481] 58: Pixel segmentation layer
[0482] 59: Organic EL layer
[0483] 60: Second electrode
Claims
1. An organic EL display device comprising, in order, a substrate, a planarization layer, a first electrode, a pixel division layer, a light-emitting pixel, and a second electrode, wherein the pixel division layer comprises a layer (A) and a layer (B), The layer (A) is a layer arranged on the surface of the first electrode so that the surface of the first electrode is partially exposed, and the layer (B) is a layer arranged on at least a part of the surface of the layer (A). The layer (A) contains a cured product of a negative photosensitive composition (a), wherein the negative photosensitive composition (a) contains: a pigment and / or a dye; a compound having two or more ethylenically unsaturated double bond groups in the molecule; and a photopolymerization initiator, and the layer (B) contains a cured product of a positive photosensitive composition (b), wherein the positive photosensitive composition (b) contains a resin and a photoacid generator.
2. The organic EL display device according to claim 1, wherein: The display portion has a portion where the area ratio of the surface of the layer (A) covered by the layer (B) is 20 to 100% of the total surface area of the layer (A) (100%).
3. The organic EL display device according to claim 1 or 2, wherein: A color filter is further provided on the light extraction side of the light-emitting pixel.
4. The organic EL display device according to claim 1 or 2, wherein: The layer (A) has an opening area of 30.0 to 260.0 μm in the display portion where the light-emitting pixels are arranged. 2 The opening of the 5. The organic EL display device according to claim 1 or 2, wherein: The cured product of the positive photosensitive composition (b) contains a resin having an imide bond and / or a benzoxazole skeleton.
6. The organic EL display device according to claim 1 or 2, wherein: The cured product of the negative photosensitive composition (a) contains the pigment, wherein the pigment contains a benzodifuranone-based black pigment represented by formula (1) or formula (2). [Chemical formula 1] [Chemical formula 2] In formula (1) and formula (2), R 1 ~R 10 Each independently represents a hydrogen atom, a fluorine atom, an alkyl group having 1 to 12 carbon atoms, a hydroxyl group or a carboxyl group.
7. The organic EL display device according to claim 1 or 2, wherein: The cured product of the negative photosensitive composition (a) further contains at least one perylene organic pigment selected from the group consisting of CI Pigment Red 123, CI Pigment Red 149, CI Pigment Red 178, CI Pigment Red 179, CI Pigment Red 190, CI Pigment Violet 29 and 3,4,9,10-perylenetetracarboxylic acid bisbenzimidazole.
8. The organic EL display device according to claim 1 or 2, wherein: The cured product of the negative photosensitive composition (a) further contains 3,4,9,10-perylenetetracarboxylic acid bisbenzimidazole.
9. The organic EL display device according to claim 1 or 2, wherein: The portion where the layer (B) is disposed on the surface of the layer (A) has a portion where the maximum film thickness of the layer (A) is 0.5 to 3.0 μm and the maximum film thickness of the layer (B) is 0.1 to 3.0 μm.
10. The organic EL display device according to claim 1 or 2, wherein: The optical density (OD / μm) of the layer (A) per 1 μm of film thickness is 0.5 to 1.
5.
11. The organic EL display device according to claim 1 or 2, wherein: The cured product of the negative photosensitive composition (a) contains silica particles having a primary particle size of 5 to 30 nm and an aspect ratio (longer diameter / shorter diameter) of 1.0 to 1.5.
Citation Information
Patent Citations
Derivatized polyhydroxystyrene having novolac type structure
JP2010106278A
Method for manufacturing vapor deposition mask, method for manufacturing organic semiconductor element and method for manufacturing organic electroluminescence display
JP2019163543A
Radiation-sensitive composition and 1,2-naphthoquinone-2-diazide sulfonic acid derivative
JP2019174793A
Norbornane-2-spiro-?-cycloalkanone-?'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic dianhydride, norbornane-2-spiro-?-cycloalkanone-?'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic acid and ester thereof, method for producing norbornane-2-spiro
WO2011099518A1
Photosensitive resin composition, method for producing heat-resistant resin film and display device
WO2014097992A1